Adaptive management: where are we now? - Rist, Lucy; Campbell, Bruce M.; Frost, Peter (Environmental Conservation, 2013)
Adaptive management (AM) emerged in the literature in the mid-1970s in response both to a realization of the extent of uncertainty involved in management, and a frustration with attempts to use modelling to integrate knowledge and make predictions. The term has since become increasingly widely used in scientific articles, policy documents and management plans, but both understanding and application of the concept is mixed. This paper reviews recent literature from conservation and natural resource management journals to assess diversity in how the term is used, highlight ambiguities and consider how the concept might be further assessed. AM is currently being used to describe many different management contexts, scales and locations. Few authors define the term explicitly or describe how it offers a means to improve management outcomes in their specific management context. Many do not adhere to the idea as it was originally conceived, despite citing seminal work. Significant confusion exists over the distinction between active and passive approaches. Over half of the studies reporting to implement AM claimed to have done so successfully, yet none quantified specific benefits, or costs, in relation to possible alternatives. Similarly those studies reporting to assess the approach did so only in relation to specific models and their parameterizations; none assessed the benefits or costs of AM in the field. AM is regarded by some as an effective and well-established framework to support the management of natural resources, yet by others as a concept difficult to realize and fraught with implementation challenges; neither of these observations is wholly accurate. From a scientific and technical perspective many practical questions remain; in particular real-world assessments of the value of experimentation within a management framework, as well as of identified challenges and pathologies, are needed. Further discussion and systematic assessment of the approach is required, together with greater attention to its definition and description, enabling the assessment of new approaches to managing uncertainty, and AM itself.
Keywords: Adaptive Management; Decision making; Natural resource management; conservation; experimental management; uncertainty

Adaptive management intentions with a reality of evaluation: Getting science back into policy - Hasselman, Lyndal (Environmental Science & Policy, 2017)
In Australia’s Murray-Darling Basin water reform has been contentious as government attempts to reconcile historical over allocation of water to irrigation with the use of water for environmental outcomes. However, in many aspects, scientific knowledge of the environment is either imperfect, incomplete or environmental responses are unpredictable, with this uncertainty preventing definitive policy and closure of political arguments. In response to uncertainty and knowledge gaps, adaptive management has been written into the legislation, along with provisions for periodic evaluation. This research ascertains how adaptive management is understood by policy makers, with this indicative of future implementation of adaptive management. The way in which adaptive management is constructed by policy makers is determined through legislation, public speeches, government reports and semi-structured interviews. The findings demonstrate that adaptive management has been subsumed by evaluation. The loss of adaptive management as a distinct concept is seen as a loss of science and discovery from the policy process, with the dominance of evaluation discussed as limiting innovation and reinforcing a ‘muddling through’ of policy.
Keywords: Accountability; Adaptive Management; Evaluation; Science; Uncertainty

Adaptive Management: From More Talk to Real Action - Williams, Byron K.; Brown, Eleanor D. (Environmental Management, 2014)
The challenges currently facing resource managers are large-scale and complex, and demand new approaches to balance development and conservation goals. One approach that shows considerable promise for addressing these challenges is adaptive management, which by now is broadly seen as a natural, intuitive, and potentially effective way to address decision-making in the face of uncertainties. Yet the concept of adaptive management continues to evolve, and its record of success remains limited. In this article, we present an operational framework for adaptive decision-making, and describe the challenges and opportunities in applying it to real-world problems. We discuss the key elements required for adaptive decision-making, and their integration into an iterative process that highlights and distinguishes technical and social learning. We illustrate the elements and processes of the framework with some successful on-the-ground examples of natural resource management. Finally, we address some of the difficulties in applying learning-based management, and finish with a discussion of future directions and strategic challenges.
Keywords: IMPORTANT

Getting intentional about M&E: choosing suitable approaches for adaptive programmes - Management, Global Learning for Adaptive (GLAM Blog, 2020)
Does the choice of monitoring and evaluation (M&E) approaches and tools matter for adaptive programmes? In short, yes: monitoring, evaluation and learning (MEL) and adaptive management (AM) are intertwined. While programme monitoring data and evaluation results are not the only sources of evidence that programmes use for learning and iteration, they often are amongst most important ones — or at least they should be. Selecting what type of information to collect and analyse — and how — is critical for any type of programme. However, what AM especially focuses on is intentionally building in opportunities for structured and collective reflection, ongoing and real-time learning, course correction and decision-making in order to improve effectiveness.

Webinar: Operationalizing Adaptive Management: What it takes. Why it matters. - Mercy Corps (Mercy Corps, 2015)
Development actors increasingly agree that managing programs adaptively – especially complex interventions – can improve their effectiveness. A growing body of evidence supports this claim. But what does adaptive management look like in practice? What does it require of managers and donors to make happen? How can we reconfigure incentives and success metrics to support adaptation, while remaining compliant?

Adaptive management: A practical guide to mitigating uncertainty and advancing evidence-based programming - Byom, K.; Ingram, M.; Oakley, A.; Serpe, L. (PACT, 2020)
Pact’s Adaptive Management Guide provides practical guidance to development practitioners globally on the mindsets, behaviors, resources, and processes that underpin an effective adaptive management system. It presents an approach to managing adaptively that is rooted in complexity analysis and program theory. It draws on Pact’s global experiences and work on topics as diverse as health, livelihoods, markets, governance, capacity development, women and youth, and more. This document begins with an introduction to adaptive management, then walks through successive steps to determine how much adaptation a project requires and how to design an appropriate system. The second half of this guidebook contains a toolkit of examples and templates that projects can tailor to their needs.

Managing to Adapt: Analysing adaptive management for planning, monitoring, evaluation, and learning - Desai, Harsh; Maneo, Gabriele; Pellfolk, Erica; Schlingheider, Annika (Oxfam, 2018)
Adaptive management is at the heart of ‘Doing Development Differently’. It emerges from stakeholders’ calls for development programmes to be more flexible and responsive to their contexts. Whether it becomes a mainstreamed practice depends on how much it is

Technical challenges in the application of adaptive management - Williams, Byron K.; Brown, Eleanor D. (Biological Conservation, 2016)
Adaptive management is an approach for simultaneously managing and learning about natural resources, by acknowledging uncertainty and seeking to reduce it through the process of management itself. Adaptive decision making can be applied to pressing issues in conservation biology such as species reintroduction, disease and invasive species control, and habitat restoration, as well as to management of natural resources in general. After briefly outlining a framework and process for adaptive management, we focus on an overview of the key technical issues related to problem framing and the ability of resource managers to learn from their experience. These technical issues include the treatment of uncertainty and its propagation over time; nonstationarity in long-term environmental trends; the applicability of adaptive management across scales; requirements for models and management alternatives that promote learning; the value of the information produced with adaptive management; the challenge to management of uncertainty and surprise; and institutional (social) learning. To accommodate these and other challenges that are now coming into focus, the learning-based approach of adaptive management will need to be adjusted and expanded in the future.
Keywords: Adaptive Management; Learning; Nonstationarity; Resilience; Uncertainty; Value of information

Managing Complexity: Adaptive Management at Mercy Corps - Mercy Corps (2015)
Managing Complexity: Adaptive management at Mercy Corps

Management not models: adaptability, responsiveness, and a few lessons from football - Maclay, Christopher (Development in Practice, 2015)
Despite a swathe of critiques of logframes and other blueprint approaches to development over the last 30 years, most aid infrastructure continues to concentrate on the design and subsequent implementation of closed models. This article does not propose an alternative to blueprints, but challenges the inflexibility of their implementation, which is inadequate given the complex nature of social change. It proposes a supplementary management and learning approach which enables implementers to be dynamic, adaptive, and responsive to problems and opportunities. Emphasising the role of donors, the paper presents a case study of one donor-led programme in Bangladesh doing just this.
_eprint: https://doi.org/10.1080/09614524.2015.983460

Passive and active adaptive management: Approaches and an example - Williams, Byron (Journal of Environmental Management, 2010)
Adaptive management is a framework for resource conservation that promotes iterative learning-based decision making. Yet there remains considerable confusion about what adaptive management entails, and how to actually make resource decisions adaptively. A key but somewhat ambiguous distinction in adaptive management is between active and passive forms of adaptive decision making. The objective of this paper is to illustrate some approaches to active and passive adaptive management with a simple example involving the drawdown of water impoundments on a wildlife refuge. The approaches are illustrated for the drawdown example, and contrasted in terms of objectives, costs, and potential learning rates. Some key challenges to the actual practice of AM are discussed, and tradeoffs between implementation costs and long-term benefits are highlighted.

Bringing adaptive management to life: Insights from practice - Arora, Anmol; Gogoi, Elizabeth; Joy, Divya; Kumar, Pankaj; Luthra, Rajni; Pal, Uma; Pervaiz, Arif (Oxford Policy Management, 2019)
The increasing popularity of adaptive programmes in the development sector in the past decade is partly a response to the complex and interconnected challenges facing many developing countries, including the impacts of climate change. The pathway to adapting to climate change is unknown, and there are many deep-rooted institutional, political, economic and social barriers. Adaptive programmes provide the flexibility to allow those delivering the technical assistance to support governments to experiment with different entry points and to adapt or change course when some are not successful. The Action on Climate Today (ACT) programme is a five-year adaptive programme that aims to strengthen systems of planning and delivery for adaptation to climate change in South Asia. As the programme draws to a close, this Learning Paper reflects on some of the major lessons learnt on the challenges and opportunities of using an adaptive programme management approach to support governments to adapt to climate change. The authors are members of the ACT implementation team, representing the management, operational and technical teams, from across different locations. The paper therefore reflects their first-hand account of the reality of implementing adaptive programmes. The paper sets out a framework for the essential ingredients of an adaptive programme management approach. These include a set of essential core principles: an evolving theory of change; a locally led and politically savvy delivery approach; experimentation and learning; and stakeholder alignment. It also includes two sets of essential resources required: management flexibility and adequate financial resources. The paper then provides learning from ACT on how to operationalise these core principles and mobilise the necessary resources. It gives detailed examples of challenges faced by ACT with regard to each component of the framework, and how the programme has overcome them, as well as retrospective reflections of additional actions the programme could have taken. A set of case studies unpacks how adaptive programme management has been operationalised in practice in particular locations. The authors are confident that the impact ACT has had owes in large part to it being an adaptive programme. The programme’s flexibility, decentralised structure and strong emphasis on learning have meant the team has been able to respond to opportunities as they have emerged and to invest time and resources where there was most potential for impact. However, this paper is also honest about the challenges ACT has faced as an adaptively managed programme. The paper therefore concludes with a set of lessons learnt from ACT for the benefit of others designing and delivering adaptive programmes on climate change and other issues.

Project facilitation as an active response to tensions in international development programmes - Lannon, John; Walsh, John N. (International Journal of Project Management, 2020)
This paper examines the tension within international development programmes between traditional task-oriented approaches to development and the wider view of programmes as sites for adaptability and learning. It characterises it as a set of inter-related tensions between recursive and adaptive tendencies that exist at individual actor, programme and institutional levels. Drawing on a multiple interpretive case study of partnership based programmes between an international non-government organisation and local partners in three countries, it looks at how these tensions play out in practice. Based on the findings, it proposes an active response to the tensions called project facilitation. This is an adaptive and co-created process that incorporates local experience and practice based knowledge to achieve strategic goals, while utilising recognised project management practices to achieve agreed outcomes. By adopting active responses to the tensions that exist within programmes it offers greater potential for effective delivery of long term benefits than the more typical defensive response strategies. Project facilitation is consistent with the social constructionist view of programmes and programme management but broadens our understanding by emphasising the need to actively consider how the tensions inherent in programmes are responded to.
Keywords: Adaptive management; International development; Non-governmental organisations; Partnership; Programme management; Project facilitation; Tensions

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Pyoe Pin, Myanmar - Christie, Angela; Green, Duncan (Itad, Oxfam and IDS, 2018)
This paper examines adaptive approaches in aid programming in a fragile, conflict and violence-affected setting (FCVAS), namely Myanmar. A combination of desk review and field research has been used to examine some of the assertions around the ‘adaptive management’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blue-print and linear project plans. This paper explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for promoting empowerment and accountability in such ‘messy places’. This case study focuses on Pyoe Pin (‘Young Shoots’), a DFID-funded, British Council managed governance programme, which has been running since 2007.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Reacting or adapting? Purposeful adaptation and response to contextual change. - Wood, Nik (Rebel with Causation, 2020)
Adaptive management is increasingly on the ticket for development programming, and has been crucial in the wake of covid-19. I’ve been working with adaptive programmes for most of my career, …

Adapting to Learn and Learning to Adapt: Practical Insights from International Development Projects - Brinkerhoff, Derick W.; Frazer, Sarah; McGregor, Lisa (RTI Press, 2018)
Adaptive programming and management principles focused on learning, experimentation, and evidence-based decision making are gaining traction with donor agencies and implementing partners in international development. Adaptation calls for using learning to inform adjustments during project implementation. This requires information gathering methods that promote reflection, learning, and adaption, beyond reporting on pre-specified data. A focus on adaptation changes traditional thinking about program cycle. It both erases the boundaries between design, implementation, and evaluation and reframes thinking to consider the complexity of development problems and nonlinear change pathways.Supportive management structures and processes are crucial for fostering adaptive management. Implementers and donors are experimenting with how procurement, contracting, work planning, and reporting can be modified to foster adaptive programming. Well-designed monitoring, evaluation, and learning systems can go beyond meeting accountability and reporting requirements to produce data and learning for evidence-based decision making and adaptive management. It is important to continue experimenting and learning to integrate adaptive programming and management into the operational policies and practices of donor agencies, country partners, and implementers. We need to devote ongoing effort to build the evidence base for the contributions of adaptive management to achieving international development results.

(Re)making the case for adaptive management - Aston, Thomas (Medium, 2022)
Great overview of what to read on adaptive management. It’s a long one, so I’ve split it into two – second installment tomorrow. Christian Aid Ireland’s recent publication The Difference Learning Makes by Stephen Gray and Andy Carl made a bit of a splash. The study found that Christian Aid Ireland’s application of adaptive programming contributed to better development outcomes and supported more flexible delivery. The much vaunted MUVA programme in Mozambique is also coming to a close and presenting its results from using and adaptive approach. So, it struck me that we might be at a critical juncture in the conversation on adaptive management. We’ve had the crashing to earth of inflated expectations in recent misanthropic reflections, [misanthropic, moi? – Duncan] alongside a fragile institutionalisation of adaptive management in donor agencies, NGOs, and private sector organisations. However, I’d argue that we’ve reached the point where adaptive management has passed the proof-of-concept stage.

Learning to Adapt: Exploring Knowledge, Information and Data for Adaptive Programmes and Policies - Workshop Summary Report - fhi360 (IDS, 2015)
Adaptive management is increasingly seen as critical capability for development programmes and policies that are more effective, efficient, relevant and sustainable. There is increasing recognition that such work requires significant changes to the organizational structures, management processes, accountability and performance cultures and indivi

Linking constituent engagement and adaptive management - Buell, Stephanie; Campbell, Megan; Pett, Jamie (Overseas Development Institute, 2020)
Constituent engagement is the two-way process of involving constituents in the design, delivery, monitoring and evaluation of programmes. Constituent engagement and adaptive management together can be a powerful combination; high-quality constituent engagement can reinforce effective adaptive management, and vice versa. By highlighting stories from leading practitioners and their organisations, this paper explores how programmes ensure that constituent engagement informs meaningful adaptation. Key messages Constituent engagement and adaptive management are both important tools for implementing responsive and effective development programmes. Together, they can be a powerful combination: input from constituent engagement can be a key source of information and evidence that meaningfully informs programme design and adaptation, and closing the feedback loop in this way increases the quality of future engagement. Both adaptive management and community engagement principles recognise that, for a programme to be effective, it must be responsive to the people meant to ultimately benefit from it. Beyond providing a key source of information for potential programme adaptations, constituent engagement efforts also help build trust with stakeholders, align expectations and promote accountability. This paper explores five key elements for ensuring that constituent engagement and adaptive management are effectively linked within a programme: strong internal systems and external channels; skilled staff that value engagement and adaptation; decision-maker champions; clear points for reflection and action; and a meaningful role for constituents.

Adaptive Management in International Development - Knowledge Base - Prieto Martin, Pedro (2025)
A curated collection of resources on Adaptive Management and MEL in International Development

Participatory adaptive management leads to environmental learning outcomes extending beyond the sphere of science - Fujitani, Marie; McFall, Andrew; Randler, Christoph; Arlinghaus, Robert (Science Advances, 2017)
Resolving uncertainties in managed social-ecological systems requires adaptive experimentation at whole-ecosystem levels. However, whether participatory adaptive management fosters ecological understanding among stakeholders beyond the sphere of science is unknown. We experimentally involved members of German angling clubs (n = 181 in workshops, n = 2483 in total) engaged in self-governance of freshwater fisheries resources in a large-scale ecological experiment of active adaptive management of fish stocking, which constitutes a controversial management practice for biodiversity and ecosystem functioning when conducted inappropriately. The collaborative ecological experiments spanned several years and manipulated fish densities in 24 lakes with two species. In parallel, we experimentally compared changes in ecological knowledge and antecedents of proenvironmental behavior in stakeholders and managers who were members of a participatory adaptive management treatment group, with those receiving only a standard lecture, relative to placebo controls. Using a within-subjects pretest-posttest control design, changes in ecological knowledge, environmental beliefs, attitudes, norms, and behavioral intentions were evaluated. Participants in adaptive management retained more knowledge of ecological topics after a period of 8 months compared to those receiving a standard lecture, both relative to controls. Involvement in adaptive management was also the only treatment that altered personal norms and beliefs related to stocking. Critically, only the stakeholders who participated in adaptive management reduced their behavioral intentions to engage in fish stocking in the future. Adaptive management is essential for robust ecological knowledge, and we show that involving stakeholders in adaptive management experiments is a powerful tool to enhance ecological literacy and build environmental capacity to move toward sustainability. Participatory active adaptive management leads to far-reaching environmental learning outcomes in stakeholders. Participatory active adaptive management leads to far-reaching environmental learning outcomes in stakeholders.

Global Learning for Adaptive Management (GLAM) - DFID (DFID Development Tracker, 2016)
To improve the value for money and impact of development interventions by promoting the use of better monitoring, evaluation and learning strategies that support development programmes to gather and respond to emergent evidence on the effects of interventions, as well as changes in the development context. The Global Learning for Adpative Management programme will make available technical assistance to DFID, USAID and partners to develop this ‘adaptive management’ approach, as well as build an evidence base to understand links between the use of adaptive management and more effective, efficient, relevant and sustainable development interventions.

Navigating complexity: Adaptive management in the Northern Karamoja Growth, Health & Governance program - Allana, Amir (MercyCorps, 2014)
Development actors increasing agree that managing programs adaptively – especially complex interventions – can improve their effectiveness. But what does adaptive management look like in practice?
Keywords: IMPORTANT; Practice

Guidance Note for Adaptive Management - Ministry of Foreign Affairs of Denmark (Government of Denmark, 2022)
This note explains what adaptive aid management is; why and when it should be considered; and how it should be applied. It covers all Danish development support channels and modalities, including bilateral country assistance, assistance to and through civil society, the private sector and to and through multilateral organisations. This guide has three chapters. Chapter 1 provides an executive overview of what adaptive management is. Chapter 2 goes deeper into five key operational principles of adaptive management. Chapter 3 details the main tenets of adaptive management processes during the programming cycle.

Celebrating Adaptive Delivery: A View from the Frontline in Myanmar - Barnes, Katrina; Lonsdale, Jane (Institute of Development Studies, 2023)
The conversation on adaptive management has grown fast amongst development actors. These conversations often focus on designing, commissioning, and managing large-scale development programmes. Exactly how this impacts the frontline, the implementers, and day-to-day project delivery is still being debated. Yet, perspectives drawn directly from practice are often largely missing within these debates. This paper is written by two development practitioners. Through this paper, we reflect on the difference between adaptive management and adaptive delivery, and how this interacts with risk and aid accountability, particularly in contexts of fragility. Drawing on examples of Oxfam in Myanmar work and our personal insights in relation to delivering programming across humanitarian, peace-building, and development, we suggest that in complex, conflict-affected, and highly political environments adaptive delivery already happens far more regularly than is currently recognised, as a necessity to get activities delivered. However, it happens despite the system, not because of it, and is therefore often hidden and carried out ‘under the radar’ rather than celebrated as a success in difficult environments. This paper was written in 2019, before the military seized control of Myanmar in February 2021. Whilst it draws on examples from pre-2021 Myanmar to illustrate real life cases, it is a contribution to a broader global debate on adaptive management in practice, specifically in fragile contexts. This is not specifically aimed at practitioners working in Myanmar at present, who are now working in a protracted crisis. This paper makes tangible recommendations on steps that donors, international non-governmental organisations, local staff, and partners could take to promote a system of encouraging and celebrating adaptability in programme delivery in fragile contexts.
Accepted: 2023-02-02T14:48:03Z

Making adaptive rigour work - Principles and practices for strenghening monitoring, evaluation and learning for adaptive management - Ramalingam, Ben; Wild, Leni; Buffardi, Anne L (ODI/GLAM, 2019)
Adaptive programmes can be accountable, rigorous and high quality in how they use evidence by taking an ’adaptive rigour’ approach. Core development and humanitarian challenges are complex, and require processes of testing, learning and iteration to find solutions – adaptive management offers one approach for this. Yet large bureaucracies and development organisations can have low tolerance for experimentation and learning, and adaptive management can be viewed as an excuse for ‘making things up as you go along’. This briefing from the Global Learning for Adaptive Management (GLAM) initiative argues that adaptive programmes can be accountable, rigorous and high quality in how they use evidence – but this requires rethinking some key assumptions about how they are practised. The paper sets out three key elements of an ‘adaptive rigour’ approach: - Strengthening the quality of monitoring, evaluation and learning data and systems. - Ensuring appropriate investment in monitoring, evaluation and learning across the programme cycle. - Strengthening capacities and incentives to ensure the effective use of evidence and learning as part of decision-making, leading ultimately to improved effectiveness.

Portfolios of Agile Projects: A Complex Adaptive Systems’ Agent Perspective - Sweetman, Roger; Conboy, Kieran (Project Management Journal, 2018)
While agile approaches can be extremely effective at a project level, they can impose significant complexity and a need for adaptiveness at the project portfolio level. While this has proven to be highly problematic, there is little research on how to manage a set of agile projects at the project portfolio level. What limited research that does exist often assumes that portfolio-level agility can be achieved by simply scaling project level agile approaches such as Scrum. This study uses a complex adaptive systems lens, focusing specifically on the properties of projects as agents in a complex adaptive portfolio to critically appraise current thinking on portfolio management in an agile context. We then draw on a set of 30 expert interviews to develop 16 complex adaptive systems (CAS)-based propositions as to how portfolios of agile projects can be managed effectively. We also outline an agenda for future research and discuss the differences between a CAS-based approach to portfolio management and traditional approaches.

Putting learning at the centre: Adaptive development programming in practice - Valters, Craig; Cummings, Clare; Nixon, Hamish (ODI, 2016)
Adaptive programming suggests, at a minimum, that development actors react and respond to changes in the political and socio-economic operating environment. It emphasises learning and the development practitioner is encouraged to adjust their actions to find workable solutions to problems that they may face. Being prepared to react to change may seem like common sense – and indeed it is. However much development thinking and practice remains stuck in a linear planning model which discourages learning and adaptation, in part because projects are seen as ‘closed, controllable and unchanging systems’ (Mosse, 1998: 5). This paper critically engages with this problem and makes clear why and how learning needs to be at the centre of adaptive development programming. It begins by clarifying why and what kind of learning matters for adaptive programming. The paper then turns its focus to how strategies and approaches applied throughout a programme’s conception, design, management and M&E can enable it to continually learn and adapt.
Keywords: IMPORTANT

Toybox's Adaptive Management in Practice - Malcolm, Emily (Toybox, 2017)
At Toybox, we understand ‘Adaptive Management’ as a broad innovative and learning approach that involves the whole organisation, our partners and funders. ‘Adaptive Programming’ of projects is part of this approach which is greatly enhanced by the Adaptive Management of all actors, including communities and children in the projects. Over the last few years Toybox have been piloting Adaptive Programming with our partners across Latin America, Africa and Asia to support children in street situations. This project has been developed within the wider context of an organisation which is focused on innovation and learning, therefore enabling Adaptive Management to become mainstream within the organisation. This paper captures the experiences and learnings of Toybox to our newly implemented Adaptive Programming approach, through the lens of a small-sized UK-based organisation working with local organisations internationally. This paper explains our learnings, inclusive of why we believe Adaptive Management is important to Toybox and how the organisation has embraced this new approach.

Adaptive Management Practice in the UK Government - The MUVA case - HLS (Human Learning Systems, 2019)
Case study about the MUVA programme in Mozambique. (Maybe it "misses the point of AP which is not learning for learning. Is learning for impact. The word impact doesn’t even come up once!") Adaptive Management programming within the Foreign & Commonwealth Development Office demonstrates that the UK Government has examples of optimising for learning within its existing management practice. However, currently, the adaptive management practices are unhelpfully framed by an approach which limits both their effectiveness and scope. The programmes use learning as their metastrategy. They succeed in connecting practicebased learning with strategic learning, and make a shift towards reframing accountability as accountability for learning. This learning strategy is enabled by funding and contract management arrangements which prioritise learning. Both at macro-level of programme management and micro level of de-risking experimentation and enabling necessary failure by decoupling people’s job security from potential failure.

Adaptive Management Leaders Launch Practical Adaptation Network (PAN) - Labs, Feedback (FeedbackLabs, 2016)
Great things can happen at the frontier of theory and practice. When Feedback Labs worked with USAID’s Global Development Lab to bring together leaders in adaptive management at the White House on June 15th, we were pleased that we were able to move past the ongoing conceptual conversations toward discussing what we could do in concrete terms to implement adaptive management in practice.

SAVI Approach Paper 11: Managing and Staffing an Adaptive Citizen Engagement Programme - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme putting learning and adaptation at the centre of all decision-making. In relation to management and staffing SAVI has established the following approaches to facilitate this: – An adaptive approach to programme management: Full time strategic technical leadership, that works closely with and complements...

Adaptive Management in Practice: a case study on the Prospects program - Maclay, Chris (Mercy Corps, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

Adaptive Management for International Development Programs - Loveridge, Donna (2007)
Capacity development, that is “the process whereby people, organisations and society as a whole unleash, strengthen, create, adapt and maintain capacity over time” (OECD 2005) has been a key aim of international aid programs. However, capacity development efforts have not met with resounding success despite approximately 25%, or USD15 billion a year, being spent by donors in recent years on technical assistance1 which has predominantly been aimed at developing capacity. A 1998 review by the World Bank (World Bank 1998) found that the success rate for capacity development efforts was between 30 – 40%. The Commission for Africa (2005) noted in 2005 that achievements were below expectations. The OECD (2007) sees capacity development as being one of the areas which are least responsive to development assistance and therefore one of the greatest challenges. This paper proposes that development practitioners and donors could benefit from taking an evaluative inquiry-type of approach to the design, implementation and monitoring and evaluation of capacity development programs. An alternative approach, “adaptive management”, is proposed. Adaptive management moves away from a rational linear A + B = C approach to capacity development towards constructing and testing theories of change2 for knowledge generation, adaptation and program improvement.

Adaptive management in aid programmes (BEAM Exchange, 2014)
Aid works better – especially in complex and conflict-affected environments – when there is scope to trial and adapt programme strategies. So argues Amir Allana in Navigating Complexity, a case study of Northern Karamoja's Growth, Health and Governance (GHG) Programme that is adopting an 'adaptive management' approach. This BEAM Exchange webinar invited Amir, Tim Sparkman and Peter Roggekamp to discuss lessons from their work in Uganda and Cambodia. What does adaptive management look like in practice? And what does it require of managers and funders to make it happen? Tim and Peter share their experiences of applying adaptive management techniques to the Growth, Health and Governance Programme and the Cambodia Agricultural Value Chain Program (CAVAC). Amir highlight insights from the Navigating Complexity report, including the importance of office culture, consistent management signals, and the role of supportive tools and processes.

Doing adaptive management at Sida - Tim Ruffer; Helen Bailey; Stefan Dahlgren; Patrick Spaven; Mark Winters (SIDA, 2019)
Lessons from the market systems development approach The evaluation focuses on Sida’s management of MSD projects. The projects are applying the MSD approach with an aim to: - contribute to improved MSD programming by Sida through better management practices across the project cycle - generate recommendations on how Sida can create conducive conditions for systems approaches and adaptive programming more generally. The brief assesses Sida’s organisational capacity for adaptive management in three dimensions: - leadership and culture - staff capacities - skills, and systems and procedures

Guidance Note: Practical introduction to adaptive management - DT Global (DT Global, 2022)
DT Global is proud to introduce our new Guidance Note: Practical Introduction to Adaptive Management There is a growing consensus around adaptive management as an effective (even necessary) approach when programs are tackling complex development problems. While there is no standard definition of adaptive management, there is general agreement that such programs need to routinely engage with and respond to program context; constantly test what works in that context; and adjust approaches, plans, and activities based on continuous learning. However, there remains a more limited body of evidence about what this looks like in practice—the enabling conditions, systems, resourcing, skills, and attitudes to effectively operationalise adaptive management. There is also limited guidance around when adaptive management is required, and to what extent—both critical and often overlooked considerations when planning for successful adaptive management. This Guidance Note draws together lessons and good practice in adaptive management from across DT Global’s diverse portfolio of donor-funded programs. It outlines our conceptual framework for adaptive management, with practical guidance on how it can be applied by our program teams. It is also designed to help our teams distinguish adaptive management from good (non adaptive) project management, consider when adaptive management is most useful on a program, and how adaptive a program (or part of a program) should be.

The Science in Adaptive Management - Ripley, Matt; Jaccard, Sabine (ILO, 2016)
‘Adaptive management’ is all the rage in international development circles. But to avoid yet another buzzword – we need to learn from the experience of natural resource science.
Keywords: IMPORTANT

The Case for an Adaptive Approach to Empowerment and Accountability Programming in Fragile Settings: Synthesis report - Christie, Angela; Green, Duncan (Itad, Oxfam and IDS, 2019)
Fragile, conflict and violence-affected settings (FCVAS) are messy and ambiguous contexts in which to plan and implement development initiatives. To work there, external actors are increasingly adopting an adaptive approach to empowerment and accountability (E&A) programming, whatever the setting. This means using a compass rather than map, where real-time political economy analysis (PEA) in relation to context and programme monitoring and evidence-informed learning in relation to intervention are used in combination and in shorter-than-usual planning cycles to maintain and adapt strategic direction. This paper brings together three case studies of large Department for International Development (DFID) governance projects in Myanmar, Nigeria and Tanzania.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Evidence-led adaptive programming: Lessons from MUVA - Sharp, Samuel; Riemenschneider, Nils; Selvester, Kerry (ODI, 2022)
Calls for more ‘adaptive programming’ have been prominent in international development practice for over a decade. Learning-by-doing is a crucial element of this, but programmes have often found it challenging to become more learning oriented. Establishing some form of reflective practice, against countervailing incentives, is difficult. Incorporating data collection processes that generate useful, timely and practical information to inform these reflections is even more so.This paper explores MUVA - an adaptive female economic empowerment programme in Mozambique. MUVA, we suggest, is atypically evidence-led. It combines systematic, inclusive reflective practice with extensive real-time data collection. We describe the fundamental features of MUVA’s monitoring, evaluation and learning (MEL) approach that supported this. One, how data collection and analysis are synchronised with set cycles for learning and adapting projects. Two, how MEL systems are designed to prioritise actionable learning, with data collection oriented more to the needs of implementing staff than to the reporting requirements of funders.This approach was enabled by building collective ownership over the programme’s objectives and the purpose of MEL from the outset. Implementers are asked about their motivations, and these are related to the programme’s Theory of Change. The evidence culture is supported by the proximity of MEL staff to implementing staff; and through structuring upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicators. We conclude by considering the relevance, or not, of MUVA’s approach to programmes in other contexts or issue areas trying to replicate a similarly evidence-informed approach to adaptive management. Key messages Learning-by-doing is essential to adaptive programming, but it can be challenging to establish data collection processes that generate useful, timely and practical information. MUVA – a female economic empowerment programme in Mozambique – has an atypically evidence-led adaptive management approach. This has two fundamental features. One, data collection and analysis are synchronised with set cycles for learning and adapting projects. Two, data collection is oriented more to the needs of implementing staff than to the reporting requirements of funders. Monitoring, evaluation and learning (MEL) systems are designed to prioritise actionable learning. This approach was enabled by building collective ownership over the programme’s objectives and the purpose of MEL from the outset. Implementers are asked about their motivations, and these are related to the programme’s Theory of Change. The evidence culture is supported by the proximity of MEL staff to implementing staff; and through structuring upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicators.

Adapting data collection and utilisation to a Covid-19 reality: Monitoring, evaluation and learning approaches for adaptive management - Ziegler, Jessica; Mason, Paige (ODI/GLAM, 2020)
This briefing note focuses on the remote collection and use of data for adaptive management during the Covid-19 pandemic, setting out key considerations to help practitioners think through a transition from more ‘traditional’ monitoring, evaluation and learning (MEL) to MEL for adaptive management (MEL4AM) that reflects the unique data collection challenges presented by Covid-19. The brief provides an overview of some key considerations in remote data collection, when this is required, and identifies other sources that address these issues in more detail. It concludes with a discussion of how to bring the information resulting from remote monitoring into decision-making to enable adaptive management. Key messages - When planning for remote data collection during the Covid-19 pandemic, first determine what information is still necessary, because data needs may have changed, e.g. if programming has pivoted or needs to pivot due to Covid-19. Then identify how the programme’s information needs align with existing data sources and what gaps remain, which will guide the need for remote data collection. - Also consider what data is ‘good enough’ for current decision-making needs in order to provide sufficient information to the right people at the right time to an acceptable standard of rigour. - There may be pragmatic reasons to reduce the number or scope of MEL activities, such as logistical constraints or ethical considerations introduced by the pandemic. - MEL activities should be accompanied by frequent feedback loops and pause points to reflect on emergent needs and challenges, information needs that have been met, and contextual changes that may affect MEL. - Be clear with decision-makers about the assumptions and gaps in the data, including proxies used and their limitations, sampling changes, and how these changes and assumptions may affect the decisions/options being discussed.

Connect. Learn. Adapt. Repeat - Practicing adaptive management in complex, conflict-affected environments: barriers and promising practices - Queen, Emily Forsyth (2018)
To shift aid culture toward adaptive management, we can: - Stay humble, empathetic, and build skills in facilitation and listening. - Focus on working with more flexible foundations or individual donors. Or, work for more rigid donors and help make their policies more flexible. - Get clearer about goals and processes while finding ways to be less specific and more committed to local leadership about pathways to get to the goal. - Resist looking for a magic adaptive management tool and instead get clearer about when teams make what kinds of decisions and matching to tools that support that decision-making. - Validate that everyone’s perspective is a form of data and try out simple ways to document how teams learns and changes. - Broaden and ground the idea of expertise – remembering that, especially when working with folx on the margins, people are the only experts on their own life. Practitioners must also examine how dominant patriarchal, white supremacist, colonial ideas have pushed us toward wanting more control, less flexibility, and less space for equitable decision making.

Contribution analysis for adaptive management - Apgar, Marina; Hernandez, Kevin; Ton, Giel (IDS/GLAM, 2020)
This briefing note shares practical learning on the use of contribution analysis for adaptive management (CA4AM). It examines how the approach enables programmes to work with theories of change in a practical, reflexive way, and how, combined with assessing evidence of a programme’s contribution to change, its findings can inform programme adaptation. It also examines both how and to what extent CA enables AM through the experiences of four large complex programmes all working towards systems-level change and employing a structured process of reflection on theories of change. Key messages CA4AM can enable programmes to work with theories of change in a practical, reflexive way. It is particularly useful for programmes operating in conditions of complexity, when it is difficult to discern attribution and when systems-level change is the goal. A range of enabling factors help CA4AM to be used most effectively, including contractual flexibility; embedded monitoring, evaluation and learning (MEL); and supportive leadership.

Listen carefully. Tread lightly. Adapt quickly. Approaching Adaptive Management: Examples from our Somalia Education Programming - CARE (CARE, 2020)
Adaptive management approaches potentially offer us opportunities to deliver high quality results in circumstances where change is complex, including in fragile, unstable or conflict affected places. However, building adaptive programming continues to be a challenge for the sector. For CARE, our Department for International Development -UK Aid funded Girls’ Education Challenge (GEC) programming has provided useful learning on how to operationalise adaptive approaches. In this paper we expand on our learning from this project and offer some recommendations for how to create more opportunities for truly adaptive programming in the future. In particular: • Projects that are designed to adapt need budget structures, results frameworks and governance that enable the process of adaptation. In our GEC projects the approaches employed by DFID, including the introduction of Review and Adaptation meetings have served to support meaningful adaptation. • Adaptive projects require both strong participatory elements and flexible governance and accountability structures. Whilst rigorous and comprehensive Monitoring, Evaluation and Learning (MEL) systems are important without these other elements appropriate adaptation can be hindered. • Adaptive Management requires resources. Where the expected change is complex, adaptation is frequently necessary to ensure we are responding to context and evidence. This should be adequately resourced if we are to expect results. In an environment where many INGOs work consistently within complex environments, the sector also needs more opportunities to trial these approaches and could benefit from more funding streams available which include the kinds of approaches used by DFID in current GEC programming

Lessons Learned From the Use of the Most Significant Change Technique for Adaptive Management of Complex Health Interventions - Ohkubo, Saori; Mwaikambo, Lisa; Salem, Ruwaida M.; Ajijola, Lekan; Nyachae, Paul; Sharma, Mukesh Kumar (Global Health: Science and Practice, 2022)
Introduction:The Most Significant Change (MSC) technique is a complex-aware monitoring and evaluation tool, widely recognized for various adaptive management purposes. The documentation of practical examples using the MSC technique for an ongoing monitoring purpose is limited. We aim to fill the current gap by documenting and sharing the experience and lessons learned of The Challenge Initiative (TCI), which is scaling up evidence-based family planning (FP) and adolescent and youth sexual and reproductive health (AYSRH) interventions in 11 countries in Asia and sub-Saharan Africa. Methods:The qualitative assessment took place in early 2021 to document TCI’s use and adaptation of MSC and determine its added value in adaptive management, routine monitoring, and cross-learning efforts. Focus group discussions and key informant interviews were conducted virtually with staff members involved in collecting and selecting MSC stories. Results:TCI has had a positive experience with using MSC to facilitate adaptive management in multiple countries. The use of MSC has created learning opportunities that have helped diffuse evidence-based FP and AYSRH interventions both within and across countries. The responsive feedback step in the MSC process was viewed as indispensable to learning and collaboration. There are several necessary inputs to successful use of the method, including buy-in about the benefits, training on good interviewing techniques and qualitative research, and dedicated staff to manage the process. Conclusion:Our assessment results suggest that the MSC technique is an effective qualitative data collection tool to strengthen routine monitoring and adaptive management efforts that allows for flexibility in how project stakeholders implement the process. The MSC technique could be an important tool for global health practitioners, policy makers, and researchers working on complex interventions because they continually need to understand stakeholders’ needs and priorities, learn from lessons and evidence-based practices, and be agile about addressing potential challenges.
Publisher: Global Health: Science and Practice

Adaptive Management looks like it’s here to stay. Here’s why that matters. - Green, Duncan (From Poverty to Power, 2016)
First installment of reflections on my US trip. This is on the rise of adaptive management approaches in USAID, and some of the questions it raises
Keywords: IMPORTANT

Bridging Learning and Action: How Did CLARISSA’s Participatory Adaptive Management Approach Foster Innovation, Effectiveness, and Stakeholder Empowerment? - Prieto Martin, Pedro; Apgar, Marina; Afroze, Jiniya; Arulanantham, Amit; Hicks, Jacqueline; Karki, Shanta; Mareschal, Sophie; Paul, Sukanta; Snijder, Mieke; Uddin, Forhad; Veitch, Helen (Institute of Development Studies, 2024)
Child Labour: Action-Research-Innovation in South and South-Eastern Asia (CLARISSA) is an evidence and innovation-generation programme funded by the United Kingdom’s Foreign, Commonwealth & Development Office (FCDO), responding to the challenge of the worst forms of child labour (WFCL) in Bangladesh and Nepal. It is a challenge characterised by a poor understanding of its drivers and a lack of evidence on what works to combat it. To handle such fundamental uncertainty, the programme adopts a child-centric and participatory action research approach, which is supported by an adaptive management model to respond better to challenges and opportunities. From its inception, the programme needed to navigate shocks and challenges, such as Covid-19 lockdowns, political upheaval, and sustained budget cuts, which put its capacity to learn and evolve to the test. This paper shares insights emerging from evaluating CLARISSA’s participatory adaptive management (PAM) practices, connecting them with current discussions on adaptive management. It provides an in-depth evaluation of CLARISSA’s PAM approach, exploring how adaptive strategies were implemented and evolved throughout the programme’s life cycle. Multiple cases of adaptation and misadaptation were selected and analysed through a series of in-depth interviews and review of programme documentation, allowing us to assess whether and how the adaptive management practices have been operationalised, the degree to which they led to enhanced decision-making and effectiveness, and their empowering effect on children and other programme stakeholders. Through conceptual analysis and real-world examples, the paper examines the key stages and critical dimensions of PAM, conveying the complexities and dynamism of adaptive management in development work, while highlighting both the successes and challenges encountered in operationalising PAM within CLARISSA.
Accepted: 2024-05-10T08:21:46Z

Applying Adaptive Management in a Fragile Context – Case Study - Lonsdale, Jane; Green, Duncan; Robertson, Kelly (DT Global, 2023)
DT Global is proud to introduce our new Guidance Note: Practical Introduction to Adaptive Management There is a growing consensus around adaptive management as an effective (even necessary) approach when programs are tackling complex development problems. While there is no standard definition of adaptive management, there is general agreement that such programs need to routinely engage with and respond to program context; constantly test what works in that context; and adjust approaches, plans, and activities based on continuous learning. However, there remains a more limited body of evidence about what this looks like in practice—the enabling conditions, systems, resourcing, skills, and attitudes to effectively operationalise adaptive management. There is also limited guidance around when adaptive management is required, and to what extent—both critical and often overlooked considerations when planning for successful adaptive management. This Guidance Note draws together lessons and good practice in adaptive management from across DT Global’s diverse portfolio of donor-funded programs. It outlines our conceptual framework for adaptive management, with practical guidance on how it can be applied by our program teams. It is also designed to help our teams distinguish adaptive management from good (non adaptive) project management, consider when adaptive management is most useful on a program, and how adaptive a program (or part of a program) should be.

Learning to Adapt: Building Adaptive Management as a Core Competency in Development Practice - Ramalingam, Ben (Institute of Development Studies, 2016)
Key messages 1. Development policies and programs increasingly operate in situations of high complexity and uncertainty. 2. There are growing efforts across the sector to design, plan and implement more adaptive responses that are more relevant and appropriate in such contexts 3. At the heart of effective adaptive programming is the capability to gather, interpret and use knowledge, information and data in real-time 4. Strengthening this capability requires a positive enabling environment—including tools and methods, structures and processes, leadership and management and culture and mindsets. 5. For adaptive development to succeed, there needs to be greater attention and investment in both knowledge, information and data systems and in appropriate enabling environments
Keywords: IMPORTANT

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Institutions for Inclusive Development, Tanzania - Green, Duncan; Guijt, Irene (Itad, Oxfam and IDS, 2019)
Adaptive Management involves a dynamic interaction between three elements: delivery, programming and governance. This case study focuses on a large DfID governance project, the Institutions for Inclusive Development (I4ID), a five-year initiative in Tanzania. The study forms part of a research project to examine whether and how adaptive approaches can strengthen aid projects promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). The research examines some of the assertions around the adaptive management approach and explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for citizen empowerment and government accountability (E&A) in FCVAS.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Agile Development in the Age of Adaptive Management - Davis, Taryn; Orton-Vipond, Sarah; Staid, Martha (Development Gateway, 2019)
Adaptive management – the idea that development projects should respond to real life complexities and be flexible enough to respond to unforeseen changes – is an often-praised approach to doing development differently, with donors and partners exploring how to apply it within their programming.

Adaptive Management: Learning and Action Approaches to Implementing Norms-shifting Interventions - McLarnon, Courtney; Gayles, Jennifer; Deepan, Prabu (USAID / Passages, 2021)
What Passages has Learned about Adaptive Management: • Be reflective about information that is collected and create a culture of learning. • Be systematic about establishing monitoring and learning systems. • Be strategic about data sources and analysis, prioritizing areas for learning and addressing issues raised. • Be inclusive about information collection: who is collecting what, how, and how is it being used.

ADAPT: Analysis Driven Agile Programming Techniques - IRC (International Rescue Committee (IRC), 2016)
A growing body of research indicates that aid agencies are most successful when able to operate flexibly, particularly in fragile environments. Yet our systems and tools are often too rigid to effectively address complex problems, and program incentives frequently undermine adaptation instead of supporting it. To drive improvements in impact we need to be better able to analyse the dynamics of a given situation, anticipate how these might evolve, and be sufficiently agile to adapt to changes in context and need.

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of PERL, Nigeria - Punton, Melanie; Burge, Richard (Itad, Oxfam and IDS, 2018)
This paper examines adaptive approaches to aid programming in Nigeria. Through field research and desk reviews, we have investigated some of the assertions around the ‘adaptive management and programming’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blueprint and linear project plans. This is the second of three case studies in a series which explore if and how adaptive approaches, including rapid learning and planning responses, are particularly relevant and useful for promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). This case study focuses on PERL (Partnership to Engage, Reform and Learn) in Nigeria, a five-year governance programme (2016-21) with a total budget of £100 million. It aims to promote better service delivery through bringing together government and citizens groups to collectively address governance challenges. PERL is viewed by DFID as the final stage of a 20-year investment, building on learning, experience and partnerships from 15 years of DFID-funded governance programming in Nigeria. It was designed to incorporate learning and adaptation through a ‘living’ theory of change, continuous political economy analysis at different levels, adaptive implementation by location-based delivery teams who are encouraged to be flexible and let partners take the lead, regular learning and reflection, and adaptive resourcing, HR and administrative systems. The case study draws on a conceptual framework (the ‘adaptive triangle’) that looks at three types of adaptation – adaptive management, adaptive programming and adaptive delivery – and the interconnections and tensions between them.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Adaptive Action: Leveraging Uncertainty in Your Organization - Eoyang, Glenda H.; Holladay, Royce J. (Stanford University Press, 2013)
Rooted in the study of chaos and complexity, Adaptive Action introduces a simple, common sense process that will guide you and your organization into reflective action. This elegant method prompts readers to engage with three deceptively simple questions: What? So what? Now what? The first leads to careful observation. The second invites you to thoughtfully consider options and implications. The third ignites effective action. Together, these questions and the tools that support them produce a dynamic and creative dance with uncertainty. The road-tested steps of adaptive action can be used to devise solutions and improve performance across multiple challenges, and they have proven to be scalable from individuals to work groups, from organizations to communities. In addition to laying out the adaptive action framework and clear protocols to support it, Glenda H. Eoyang and Royce J. Holladay introduce best practices from exemplary professionals who have used adaptive action to meet personal, professional, and political challenges in leadership, consulting, Alzheimer's treatment, evaluation, education reform, political advocacy, and cultural engagement―readying readers to employ this new toolkit to meet their own goals with a sense of ingenuity and flexibility.

Adaptive development: great progress and some niggles - Vowles, Pete (Medium, 2016)
After 3 years in DFID headquarters, championing adaptive approaches to the delivery of aid and development programmes, I am back in an…

Civil society organizations and managerialism: On the depoliticization of the adaptive management agenda - Gutheil, Lena; Koch, Dirk-Jan (Development Policy Review, 2022)
Motivation In the last decade, a movement formed around making aid delivery more adaptive, relying on principles such as context sensitivity, flexibility, and ownership. The approaches seem promising for civil society organizations (CSOs) to fulfil their mission of fostering social transformation. While several donor agencies have started engaging with such approaches, the authors hardly see their political implications in practice. Purpose The article aims to provide evidence on an adaptive project and demonstrate how the social transformative and political nature of adaptive development management is rendered technical and depoliticized in practice. Methods and approach We use a case study of a development programme based on a social transformative policy framework that is implemented through CSOs in Uganda and Vietnam. Data were collected by means of interviews, participant observation and document analysis. Findings We find that, in practice, the social transformative policy framework is competing with managerial logics. We compare this process with the depoliticization of the Paris Declaration on Aid Effectiveness, finding striking similarities. By using practice theory, we show how managerialism remains the dominant paradigm in the civil society aid sector, fuelling the “anti-politics machine.” Policy implications The article shows that policy frameworks do not always work as intended. Donors should therefore not only change policy frameworks, but also start addressing institutional and operational requirements.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dpr.12630

Implementing adaptive management: A front-line effort — Is there an emerging practice? - Teskey, Graham; Tyrrel, Lavinia (Abt Associates, 2021)
Among the many principles that currently inform donor-funded development initiatives, three appear to stand out: they should be politically informed, locally led, and adaptive. There is as yet little practical guidance for aid implementers regarding how to operationalise these approaches. What will it take to shift practice away from linear and planned approaches, towards models which foster local leadership and which engage with emergent and complex systems? This paper suggests that the answer is not to throw out the discipline of the logical framework, results frameworks, or theories of change. Rather they need to be handled rather more reflectively and ‘elastically’. The purpose of this paper is to set out how this can be achieved, and to propose 15 tools for donors, implementors and front-line staff to apply adaptive management (AM) in practice, at critical stages of the project cycle and within the dominant aid paradigm. This is what we are calling PILLAR: politically informed, locally led and adaptive responses. We are framing PILLAR to cover the full project cycle (design, implementation and review), hence the nomenclature of an ‘end to end’ approach. Our hope is that these tools will eventually replace the current planned, log-frame driven and top-down approach to aid design and delivery which dominates the development sector.

Capacity Development in a Participatory Adaptive Programme: the Case of the Clarissa Consortium - Widmer, Mireille; Apgar, Marina; Afroze, Jiniya; Malla, Sudhir; Healey, Jill; Constant, Sendrine (Institute of Development Studies, 2022)
Doing development differently rests on deliberate efforts to reflect and learn, not just about what programmes are doing and achieving, but about how they are working. This is particularly important for an action research programme like Child Labour: Action- Research-Innovation in South and South-Eastern Asia (CLARISSA), which is implemented by a consortium of organisations from across the research and development spectrum, during a rapidly changing global pandemic. Harnessing the potential of diverse skills and complementary strengths across partners in responding to the complex challenge of the worst forms of child labour, requires capacity to work together in novel ways. This Research and Evidence Paper documents how CLARISSA approached capacity development, and what we learnt from our challenges and successes. From the start, the programme incorporated a capacity development strategy resting on self-assessment of a wide range of behavioural and technical competencies that were deemed important for programme implementation, formal training activities, and periodic review of progress through an after-action review (AAR) process. An inventory of capacity development activities that took place during the first year of implementation reveals a wide range of additional, unplanned activities, enabled by the programme’s flexibility and adaptive management strategy. These are organised into eight modalities, according to the individual or collective nature of the activity, and its sequencing – namely, whether capacity development happens prior to, during, or after (from) implementation. We conclude with some reflections on the emergent nature of capacity development. Planning capacity development in an adaptive programme provides a scaffolding in terms of time, resources, and legitimacy that sustains adaptiveness. We also recognise the gaps that remain to be addressed, particularly on scaling up individual learning to collective capabilities, and widening the focus from implementation teams to individuals working at consortium level.
Accepted: 2022-04-25T10:25:54Z

Adaptive Programming: The “Space of Possibility” - Seavey, Sara Mizuta (USAID Learning Lab, 2016)
Sara Mizuta Seavey, M.A., is a Senior Program Officer at FHI360 for the Mobile Solutions Technical Assistance and Research (mSTAR) project, where she works with USAID’s Digital Development Team to conceive, design, and test how real-time data systems can enable a more adaptive and participatory approach to development. She is passionate about systems thinking and participatory approaches to international development. What does space travel have to do with international development?

Monitoring for problem-solving, adaptive management, reporting and learning - Dominique Morel; Dzino-Silajdzic, Velida; Hagens, Clara (Catholic Relief Services, 2020)
Internal and external stakeholders have different information needs over a project’s life, for purposes that include adaptive management, accountability, compliance, reporting and learning. A project’s monitoring, evaluation, accountability and learning, or MEAL, system should provide the information needed by these stakeholders at the level of statistical reliability, detail and timing appropriate to inform data use. In emergency contexts where the situation is still fluid, ‘informal monitoring’ has proved helpful to staff’s ongoing assessment of the broader environment in order to identify changes in the situation, in other actors’ responses, and in priority unmet needs that would require corresponding changes in the response.2 The same distinction between informal monitoring of possible changes in the project’s operating context—whether identified as project assumptions and risk factors or not—and formal monitoring of the activities included in the response and project indicators, is relevant for development contexts too. Informal monitoring: Ongoing assessment of changes in operating context Formal monitoring: Tracking progress against project activities and indicators Within formal monitoring, it is useful to further differentiate between light monitoring and rigorous monitoring: - Light monitoring aims to provide timely feedback on new activities (or new locations or target groups) or aspects of the project’s theory of change (activity-to-output or output-to-IR change) logic that staff are less confident about, to check for early signs that progress is being made and that assumptions are holding true while there is still ample time to make adjustments if necessary.3 - Rigorous monitoring aims to collect representative data for evidence-based project management, reporting and learning, not just at midterm but throughout project implementation.

+Acumen MOOC: Adaptive Leadership: Mobilizing for Change and Disrupting the Status Quo - +Acumen (NovoEd, 2017)
This four-module course by +Acumen and Adaptive Change Advisors on adaptive leadership, which is a practical leadership framework developed at Harvard Kennedy School for driving systemic change, particularly during times of uncertainty or when there are no easy answers.

Doing Digital Development Differently: Lessons in adaptive management from technology for governance initiatives in Kenya - Prieto Martin, Pedro; Hernandez, Kevin; Faith, Becky; Ramalingam, Ben (IDS, 2017)
Development projects don’t always work as planned. This has long been acknowledged by those in the sector, and has led to several approaches that seek to solve complex development problems through enabling and encouraging greater adaptiveness and learning within projects (e.g. Doing Development Differently and Problem-Driven Iterative Adaptation). Digital development projects experience many of these issues. Using technology for transparency and accountability (Tech4T&A) projects in Kenya as case studies, our research analysed the many different theoretical approaches to learning and adaptation, and then tested how these play out in reality. Firstly, we conducted an extensive review of the literature on the spectrum of approaches to adaptive learning. The findings were used to develop a framework through which to analyse adaptiveness at the different layers of complexity in projects (e.g. software design and development, programme design and management). The second part of the research consisted of interviews and focus group discussions with participants in Tech4T&A projects in Kenya. Respondents helped us identify the main characteristics of adaptiveness in their projects (e.g. who needs to adapt, and how and when) and the challenges and issues that inhibit projects’ abilities to be adaptive. This process also revealed how accountability interplays with adaptiveness, and considered how better collaboration flows can enable adaptiveness. From our literature review and empirical study, we draw several conclusions for increasing adaptiveness in digital development projects. These include simplifying the many adaptive theories that abound, increasing responsiveness to project beneficiaries and stakeholders, and for stakeholders to keep on experimenting, networking and advocating.
Keywords: IMPORTANT

Adaptation in practice: lessons from teenage pregnancy programmes in Sierra Leone - Castillejo, Clare; Buell, Stephanie (ODI, 2020)
A discussion of initial learning emerging from the SLRC ’Adaptive approaches to reducing teenage pregnancy in Sierra Leone’ action research project.

5 Principles to Guide Adaptive Leadership - Ramalingam, Ben; Nabarro, David; Oqubuy, Arkebe; Carnall, Dame Ruth; Wild, Leni (Harvard Business Review, 2020)
How you respond to a crisis will have repercussions for years to come. The Covid-19 pandemic is constantly evolving, with leaders facing unpredictability, imperfect information, multiple unknowns, and the need to identify responses quickly — all while recognizing the multi-dimensional (health-related, economic, social, political, cultural) nature of the crisis. Responding to the crisis requires adaptive leadership, which involves what we refer to as the 4 A’s: Anticipation of likely future needs, trends and options. Articulation of these needs to build collective understanding and support for action. Adaptation so that there is continuous learning and the adjustment of responses as necessary. Accountability, including maximum transparency in decision-making processes and openness to challenges and feedback.
Keywords: Crisis management; Leadership

Nimble adaptation: Tailoring monitoring, evaluation, and learning methods to provide actionable data in complex environments - Serpe, Lauren; Ingram, Mason; Byom, Kate (New Directions for Evaluation, 2022)
This chapter examines good practices in implementing effective Monitoring, Evaluation, and Learning (MEL) systems within complex international development Democracy, Human Rights, and Governance (DRG) programs, which are characterized by challenges of non-linearity, limited evidence of theories of change, and contextual and politically contingent nature of outcomes. The chapter presents three cases of MEL systems in complex projects implemented by Pact across distinct and diverse operating contexts – Zimbabwe, Cambodia, and Somalia – to illustrate those projects’ MEL approaches that enabled continuous adaptation. The authors analyze the cases to respond to two questions: (1) What are the key elements of effective adaptive management-focused MEL systems in complex environments? (2) What is practical guidance for designing and enabling complexity-responsive and effective adaptive management-focused MEL systems? The case studies illustrate three key elements: (1) Information gathering that closely links context, research, and performance data; (2) Systems for reflection that offer scheduled learning moments of varying frequency and intensity, as well as multiple feedback mechanisms; and (3) Enabling structures that promote adaptive mindsets and attitudes within project teams.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/ev.20523

Study on application of Adaptive Management (AM) in Education Out Loud (EOL) project implementation in the Horn, Eastern adn Southern Africa (HESA) - ANHRE (Oxfam, 2022)
This study mainly aimed to look at adaptive management in the program cycle (throughout Program Cycle processes, including strategy, project, and activity design and implementation) and to look at the Enabling Conditions: how an organization’s culture, business processes, and resource allocation support adaptive management. It explores elements of adaptive management that correspond to the objectives of the study as follows: 1) Assess grantees’ level of understanding of adaptive management as a programming approach and a method of risk mitigation Methodology. 2) Examine how adaptive management has been applied in EOL project implementation thus far. 3) Explore ways in which an adaptive management approach can be used as a source of learning during project implementation. 4) Propose ways in which the application of adaptive management can be improved in EOL project implementation. Objective 1: Assess grantees’ level of understanding of adaptive management as a programming approach and a method of risk mitigation Methodology: The researchers asessed whether the EOL program, GMU, and HESA RMU have a culture of openness, continuous learning, reflection, and improvement. This assessment looked at actual practices and perceptions of field-based staff and project officers. In addition, they looked at processes to assess knowledge management and decision-making process – the ability to distill, share and disseminate knowledge and the awareness among grantees/ employees of the decision-making process. Summary of findings: Understanding of adaptive management as a programming approach among the selected sample of grantees was linked to continuous learning, the ability to adjust implementation and inform decision making to reach the intended objectives based on analysis and assessment of the context and flexibility in management. RMU HESA was perceived to have a culture of openness where grantees feel comfortable sharing their opinion and ideas and is perceived to be receptive to proposed changes to projects and encourage grantees to provide feedback. The HESA RMU-Oxfam Denmark is also seen as an agency that is very “flexible“. Recommendations: Enhance Capacity building on adaptive management tools, particularly for finance and admin teams with a focus on pro-active adaptive management which scans the horizon for opportunities and risks, and it adapts to take advantage of them. It explicitly plans for experimentation and regular upgrading of the strategies; it considers learning and the reduction of uncertainty and imperfect knowledge as one of the key objectives of the management effort. Objective 2: Examine how adaptive management has been applied in EOL project implementation thus far Methodology: Two elements were assessed : Collaboration and how internal and external collaboration of grantees and grant agent, assessing the ability to collaborate with other departments within the entity, the ability to collaborate with learning partners, other grantees, to what extent they consult their stakeholders and their ability to build coalitions. In addition, researchers looked at Adaptation and the best practices and lessons learned in adopting change in the design, implementation, budgeting or monitoring of EOL programs and the process followed to adapt the desired change. Summary of findings: Adaptive management practices are seen to be adapting to context changes, constant learning, and flexibility. The management and coordination of EOL program is deemed to be collaborative, adaptive, and understanding of the emerging needs of EOL Program implementation. There is a simple process in place for grantees to make changes to the program implementation. Most grantees do take the time to pause and reflect on what is going well and what could be improved and to share the knowledge gained with their coalition members and regional coalitions. HESA RMU was found to be encouraging learning practices through organizing periodic online and offline regional learning and reflection workshops. Compared to other donors, the majority of grantees believe that EOL provided the highest level of flexibility and ability to adapt which is seen to be a necessity for advocacy work. However, it is important to enforce structure to tighten the feedback loop between data and action: adaptive management aims for double learning more than just correcting deviations in planned versus actual. Recommendations: Introducing outcome harvesting tool as one of the mechanisms to capture outcomes, institutionalization of adaptive management further by developing context analysis tools/ regular reviews of TOC. Further use of Scenario planning as a tool to map and plan different scenarios on how change may happen, and to examine the program’s role in making future events happen, enforcing structure to tighten the feedback loop between data and action. In addition to the introduction of quarterly planning cycles where data and information gathered in the previous quarter can be used to inform the next planning cycle and update the TOC, project design and activity implementation strategies. Objective 3: To explore ways in which an adaptive management approach can be used as a source of learning during project implementation Methodology: The team assessed the grantees’ ability to use evidence to build their pathways for change, their ability to use learning to inform decision making, the frequency and habit of reviewing their theory of change, the risks and opportunities through scenario planning, how they assess the efficiency of their data collection tools and monitoring and evaluation data quality, on whether they have a mechanism to monitor unintended outcomes (outcome harvesting) and reflect. Summary of findings: This study revealed that there is a culture of collaborating, learning and openness among grantees and HESA RMU. The EOL program has adopted Re-active Adaptive Management that relies on regular monitoring and reflection activities to detect unpredicted challenges and, when needed, to adjust planned actions to remain on track to achieve the desired program outcomes. EOL provided learning opportunities, platforms for knowledge sharing and encouraged peer learning among grantees. Recommendations: Encouraging further engagement on knowledge sharing hubs and investing in knowledge transfer on adaptive management and learning to other partners in targeted countries (EOL to become an influencer in this field), encouraging further engagement from learning partners to provide mentorship and support during implementation and continuous learning on adaptive management tools. RISP and GISP could be further engaged in the monitoring process. Based on the stated objective, what was assessed and findings, it would also be interesting to enable grantees distill learnings from AM practices and applying that knowledge to improve project implementation. This means AM will be expected to go beyond changing implementation strategies and budgets and document learnings from such changes and apply them to improve the remaining part of the project. Objective 4: Propose ways in which the application of adaptive management can be improved in EOL project implementation Summary of findings: Grantees were able to articulate well their understanding of adaptive management but were less able to provide concrete examples of how adaptive management is implemented in practice. There is a culture of collaborating, learning and openness among grantees and HESA RMU. The EOL program relies on regular monitoring and reflection activities to detect unpredicted challenges and, when needed, to adjust planned actions to remain on track to achieve the desired program outcomes. EOL provided learning opportunities, platforms for knowledge sharing and encouraged peer learning among grantees. However, it is important to enforce structure to tighten the feedback loop between data and action and to institutionalize practicing adaptive management. Recommendations: A roadmap that looks at reviewing seven steps for improving adaptive management is recommended as a systematic tool to introduce improvement. This roadmap is useful in a multi-organizational, multi-country set-up where efficient design is needed to align top-down structuring and requirements with bottom-up diversity and divergence. This roadmap of seven steps is introduced by HIVOS. These 7 steps can come in a different order and it depends on the user to assess which of the seven steps needs to be undertaken. 1. Annual Review results/ outcome statements: using outcome harvesting to continuously monitor intended/ unintended outcomes (whether positive or negative or within the sphere of control (outputs) or within the sphere of influence (outcomes). 2. Learning questions: Learning from the monitoring data; Learning about the critical Make-or-Break assumptions in the Theory of Change; and Developing learning topics/ questions and learning agenda at each level 3. Changes in context: Identifying possible trends and signs about emerging shifts in the environment, followed by analyzing and collective sense-making of possible implications for the Theory of Change (is there a need to revise intervention strategies, desired outcomes, pathways, assumptions? 4. Theory of change: Reviewing the theory of change was not seen as a frequently recommended practice. Constant validation of pathways to change and evidence in the TOC is important. 5. Capacity assessment and development: What capacities are available amongst the alliance members and partner organizations in relation to the (revised) Theory of Change; What would be Capacity Development needs in view of the capacity assessment results? 6. Strategies and interventions: With the outcomes achieved and learning so far, what can you say about your interventions and strategies? What worked? Why? Is there a need for adjustment? 7. Annual reflection and Planning Who should take part in the annual planning and reflection?

What is adaptive management? - Wilson, Gregory (ΔNTYLLES, 2016)
Recently there has been growing recognition that most development challenges are in actual fact ‘wicked’ problem that requires development actors to recognize that the optimal management approaches…

Agile Software Development: Adaptive Systems Principles and Best Practices - Meso, Peter; Jain, Radhika (Information Systems Management, 2006)
Today's environments of increasing business change require software development methodologies that are more adaptable. This article examines how complex adaptive systems (CAS) theory can be used to increase our understanding of how agile software development practices can be used to develop this capability. A mapping of agile practices to CAS principles and three dimensions (product, process, and people) results in several recommendations for “best practices” in systems development.
Keywords: IMPORTANT

Implementing Adaptive Approaches in Real World Scenarios: A Nigeria Case Study, with Lessons for Theory and Practice - Bridges, Kate; Woolcock, Michael (The World Bank, 2019)
How does adaptive implementation work in practice? Drawing on extensive interviews and observations, this paper contrasts the ways in which an adaptive component of a major health care project was implemented in three program and three matched comparison states in Nigeria. The paper examines the bases on which claims and counterclaims about the effectiveness of these approaches were made by different actors, concluding that resolution requires any such claims to be grounded in a fit-for-purpose theory of change and evaluation strategy. The principles of adaptive development may be gaining broad acceptance, but a complex array of skills, expectations, political support, empirical measures, and administrative structures needs to be deftly integrated if demonstrably positive operational results are to be obtained, especially when undertaken within institutional systems, administrative logics, and political imperatives that are predisposed to serve rather different purposes.

SAVI Approach Paper 12: Managing Programme Finances to Support Adaptive, Locally-led Processes of Citizen Engagement in Governance - SAVI (DFID, 2016)
SAVI, is seeking to support processes of citizen engagement in governance in ways that are effective in influencing reform, and that are able to take on a life of their own without continuing donor support. SAVI is also an adaptive programme, putting learning and adaptation at the centre of all decision-making. Money is used and...

Top Tips: How to design and manage adaptive programmes - Valters, Craig; Wild, Leni (Overseas Development Institute, 2019)
Within DFID, there is now a commitment to more flexible and adaptive programming. This recognises that: • DFID works in contexts that continuously evolve and change, sometimes in unpredictable ways. To respond to this, the agency needs to remain flexible – to expect change and have a good understanding of context, with resources that can be adjusted and scope to change direction if needed. All DFID programmes should be able to do this. • Some DFID programmes aim to support change in complex systems, behaviours and incentives. Efforts to address women’s empowerment, improve sanitation or build more sustainable health systems, for instance, all require engagement with the way in which complex systems operate and the people and behaviours within them. Trying to deliver reforms in these circumstances is challenging because the pathway to reform itself will be unclear: as a reform is rolled out, the system itself will react and respond. These types of programmes therefore need to build in from the start deliberate processes of learning and testing, to allow for adaptations as more information is gathered for what works over time. These top tips are concerned with programmes that aim to be flexible and adaptive – which work in dynamic contexts and are trying to address complex problems. While there is growing commitment to these approaches, feedback suggests staff still have questions about how to do this well. This document highlights some of the commonly reported issues related to adaptive programming and a set of tips, strategies and examples to help in addressing them. It is aimed at programme managers and advisors who may be Senior Responsible Owners (SROs) or those managing and supporting adaptive programming in a range of ways. We have collated these lessons from discussions with country offices and SROs, feedback from surveys and the wider evidence. We have looked specifically at the adaptive programmes we can find in the DFID portfolio, but this is not an exhaustive list. It should be noted that there is as yet no wide variety of case law to review, but there is a growing set of examples within DFID that can provide continuous learning for the organisation.

Program Cycle - Discussion Note: Managing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Value for money and adaptive programming - Approaches, measures and management - Laws, Ed; Valters, Craig (ODI, 2021)
- The United Kingdom’s Foreign, Commonwealth and Development Office (FCDO)’s standard economy, efficiency, effectiveness/cost-effectiveness and equity (4E) framework is still relevant for approaching, measuring and managing value for money (VfM) for adaptive programmes. • However, this framework needs to be reframed to capture and incentivise flexibility, learning and adaptation. • VfM appraisal and reporting should be done in a way that draws on beneficiary feedback and informs good decision-making, rather than just being a compliance exercise. • If VfM appraisal and reporting cannot be done appropriately for adaptive programmes, it should be avoided or minimised. There is a risk of diverting time and resources from more suitable tools and methods.

Adaptive Programming and going with the grain: IMAGINE's new water governance model in Goma, DRC - Kirk, Tom; Green, Duncan; Stys, Patrycja; Mosquera, Tom (Development Policy Review, 2023)
Motivation This paper explores adaptive approaches to development programmes that aim at improving service provision in underperforming sectors in fragile and conflict affected states (FCAS). It does this through a case study of the Integrated Maji Infrastructure and Governance Initiative for eastern Democratic Republic of the Congo's (IMAGINE) public-private partnership model for water provision. Purpose The processes and decisions that culminated in IMAGINE's model emphasize the need for programming that is culturally and politically aware, responsive to events, learns in real-time, is entrepreneurial, and works with the grain of local institutions to support change. Detailed case studies of such ways of working are crucial for programmes that seek to challenge and reform the status quo in FCAS. Methods and approach The paper is based on 42 semi-structured interviews conducted in the summers of 2019 and 2020. They reflect the broad spectrum of actors – individuals, public authorities, and organisations – involved in IMAGINE's evolution. Findings The narrative focuses on IMAGINE's attempts to professionalise and commercialise Goma's water sector. It shows how as IMAGINE repeatedly adapted to ground realities, it took on the characteristics of a public authority, thereby, engendering backlashes that threated its longer-term goals. However, by revisiting its initial values and logics it was able to get things done and achieve it aims. Policy implications IMAGINE's story suggests that adaptive programmes should put politically savvy local development professionals in key positions and enable them to carefully construct coalitions of allies across the systems they aim to disrupt. This may also require them to revisit and adapt their initial ideas, guiding principles and values as greater understandings of development problems are gained. A pubic authorities lens, attuned to the logics programmes seek to address and introduce to FCAS, may help analysts to foreground the implications of such adaptations.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dpr.12691

Learning and adapting: the use of monitoring and evaluation in countering violent extremism: a handbook for practitioners - Dawson, Laura; Edwards, Charlie; Jeffray, Calum; Royal United Services Institute for Defence and Security Studies (Royal United Services Institute for Defence and Security Studies, 2014)
IN 2013, the Royal United Services Institute for Defence and Security Studies (RUSI) was awarded a grant under the Kanishka Project to develop a handbook for monitoring and evaluating counter violent extremism (CVE) policies and programmes. The aim of this handbook is to support CVE policy-makers and practitioners (those who design, manage and evaluate CVE programmes), by providing them with key terms regarding violent extremism and radicalisation, describing the purpose of evaluation, and providing examples of key methodologies they can employ to conduct monitoring and evaluation (M&E) in this emerging policy field. The handbook will enable readers to understand why, when and how to conduct an evaluation of a CVE policy, programme or project. .
OCLC: 1079851950

Monitoring and learning for country-level portfolio decision-making and adaptation - Buffardi, Anne L; Mason, Paige; Hutchings, Claire; Sharp, Samuel (ODI/GLAM, 2019)
Most measurement and adaptive management approaches were developed for and from individual projects. This briefing aims to guide measurement and management of country-level portfolios of work. It identifies potential purposes portfolio-level analyses can fulfil, types of adaptation, and the relative role of monitoring, learning and evaluation (MEL). Drawing on reviews of practice from the United States Agency for International Development (USAID) and the United Kingdom Department for International Development (DFID), guidance notes, and experiences of members of the Global Learning for Adaptive Management (GLAM) initiative, it offers recommendations and considerations that are particularly relevant for this level of analysis and management. Key messages - Portfolio-level analyses can serve eight potential purposes, each of which answers different questions, involves adaptation at different times and levels, and requires different types of evidence. Identifying the purpose(s) and how the component parts relate to each other should guide the development of monitoring and learning systems. - Portfolios are oriented more towards breadth than depth, involve more people with different perspectives, and draw on multiple sources of evidence with potentially greater variation in quality. - In practice, four activities appear to be applied most frequently at a portfolio level: alignment of indicators and aggregation of monitoring data; synthesis of multiple sources and types of information to provide a summary of outputs, outcomes, common observations and trends; periodic review and reflection sessions; and strategic planning, design or refresh of the portfolio strategy. - The extent to which evidence-informed portfolio management is facilitating learning and adaptation has not been well documented to date, and we suggest potential indicators to do so.

Opportunities and challenges for DAC members in ‘adapting to context’ - Sharp, Samuel; Wild, Leni (2021)
Key Messages New principles for OECD DAC members on ‘Managing for Sustainable Development Results’ emphasise tailoring result management approaches to different contexts; balancing internal compliance with empowerment at ground level; and adapting implementation in the pursuit of long-term outcomes. However development organisations face numerous challenges in aligning with these principles in practice. Reporting and evidence collection processes do not consistently encourage adaptive practice, reflecting their orientation towards accountability over learning. Context analysis is common during programme design, but used less on an ongoing basis. Popular tools –such as logical frameworks and theories of change - are often intepreted in linear ways, not as ‘living documents’ that react and change over time. Organisations need to meaningfully empower staff to work adaptively, including examining incentives and cultures that can make staff more comfortable with traditional results management. Even when senior leadership is supportive of adaptive ways of working, they can lack a clear understanding of the resourcing required and appropriate governance and management processes. Development organisations and their partners have attempted to address these challenges through the use of different monitoring and evaluation tools and methods, changes to reporting frameworks and templates, and initiatives to create positive incentives and motivate staff, leadership and partners at different levels.
Keywords: _tablet

USAID Wildlife Asia as a case study in adaptive rigour - Ziegler, Jessica (ODI/GLAM, 2020)
This briefing note looks at how the United States Agency for International Development (USAID) Wildlife Asia programme has operationalised the concepts of adaptive rigour and adaptive management as part of its approach to collaborating, learning and adapting. As described by the Global Learning for Adaptive Management (GLAM) initiative, adaptive rigour is about ensuring that the data, information, methods, processes and systems that underpin adaptive management are robust, systematic and high‑quality. Key messages When faced with programmatic complexity, it is important to take an adaptive approach driven by continuous and iterative monitoring, evaluation and learning (MEL). USAID Wildlife Asia, which works to advance regional action towards ending illegal wildlife trafficking in Southeast Asia and China, has embraced this approach as a way of operationalising adaptive rigour. Throughout programming, MEL approaches should reflect the characteristics of adaptive rigour: comprehensiveness, usefulness, practicality, timeliness and support. Utilising performance monitoring and research in order to test and revise technical approaches and employing mixed methods to collect both qualitative and quantitative data, as well as looking for relevant lessons generated by others, can ensure access to the most useful information for decision-making throughout implementation. For adaptive management, it is not enough to monitor, evaluate and learn; it is also essential to pause and reflect in order to analyse and process evidence gained through MEL with colleagues and stakeholders to reach the right conclusions and make good decisions.

LearnAdapt: a synthesis of our work on adaptive programming with DFID/FCDO (2017–2020) - Laws, Ed; Pett, Jamie; Proud, Emma; Rocha Menocal, Alina (ODI, 2021)
Key takeaways. • Development is not linear or straightforward, but rather complex, uncertain and context-specific. This calls for international development actors to work differently, in ways that are based on deliberate experimentation, learning and adaptation, to inform decisions and drive effective development. • Although it might go by different names, adaptive programming has been used in a variety of areas and fields in both the public and private sectors. Development practitioners have much to learn from and contribute to these different approaches and experiences. • Trust and relationship-building across all relevant stakeholders are among the most critical enabling factors for adaptive management. They are essential to give partners the space, autonomy and authority needed to try, test, reflect, iterate and feed back at the frontline of implementation, and to give donors the confidence that decisions are being made on the basis of evidence and learning to improve effectiveness. • There is an urgent need to rethink how accountability requirements, results frameworks, value for money considerations, performance markers, procurement and contracting mechanisms and other processes are understood and applied so that they are better aligned with and can support adaptive management more effectively. • The role of senior managers leading adaptive programmes from the donor side should be to create a space for experimentation and learning. Funders should hold their partners accountable for learning and how it feeds into effective programming, rather than for delivering on predetermined targets. • While formal guidance is important, leadership, champions, institutional incentives, a supportive management culture and appropriate mindsets are essential to encourage adaptive ways of working. • Adaptive management is resource-intensive. It requires skill, commitment, time for building trust and investments in learning. It is a journey, not an immediate destination – so it calls for patience, open-mindedness and a more nuanced approach to risk.

Built to improve: Leveraging realtime M&E for adaptive youth employment programming - Skelton, John (Mercy Corps, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

Adaptiveness through ‘simplest tools and practices’ - Prieto Martin, Pedro (Institute of Development Studies, 2017)
In recent years, more and more influential development organisations have been openly recognising the central role that adaptive management capacities – the ability to keep improving strategies and actions as programmes unfold – play for the success of complex interventions. As a result, there has been a rich exchange of ideas and experiences on how to promote adaptiveness in development. But development organisations and professionals are having a hard time translating the many adaptive theories and recommendations into improved practices and outcomes. They are generally failing to adjust the design and operation of programmes to accommodate incipient lessons learnt and the unexpected changes in the context. Nowadays, most programme adaptations still take the form of a change of direction once it is clear that things have gone really wrong. Why is so difficult to put what we know about adaptiveness into practice? And more importantly: what can be done to improve this situation?

Help! I’m hiring new staff and I want them to work adaptively. A guide to hiring adaptive employees. - Salib, Monalisa (USAID LEARN, 2019)
If you are involved in hiring, this tool can help you increase your chances of selecting staff members skilled in adaptive management. It will help answer the questions: Which competencies should I recruit for in order to hire more adaptive employees? Which desired qualifications should I incorporate into position descriptions to attract adaptive employees? Which interview questions should I ask to screen for adaptive employee competencies? You should use this tool when you decide to hire a new individual - whether that be a direct hire, contractor, or consultant - or when you are changing an individual’s current position description or scope of work. Specifically, this tool will help you determine which qualifications are most important for the position and offers interview questions you can use with candidates. — You’re in luck! We just released a new guide for hiring adaptive employees. This visual and user-friendly tool will help increase your chances of selecting staff skilled in adaptive management. Here are the details: What do you mean by “work adaptively” or an “adaptive employee”? An adaptive employee is an individual who, in collaboration with relevant stakeholders, systematically acquires and uses knowledge to make decisions and adjustments in their work in order to achieve greater impact. Why focus on adaptive employees? Why does it matter? With industries, technologies, and organizations in a near constant state of flux, leaders are recognizing the importance of adaptability as a critical capacity. Because of this, it’s not surprising that a recent LinkedIn report found that adaptability was the most important soft skill hiring managers were screening for. In addition, evidence shows that teams that apply more data-driven and adaptive leadership practices perform better than those that focus less on these practices. It makes sense, then, that managers want to recruit more team members who are skilled in adaptive management - it helps achieve results. Who should use this tool? Anyone involved in hiring, responsible for developing or approving position descriptions, participating in interviews, and/or approving new hires. When should I use this tool? Use it as soon as you decide to hire a new staff person or when you’re adjusting existing position descriptions. What does the tool help me do? It will help you think through: Which competencies should I recruit for in order to hire more adaptive employees? Which desired qualifications should I incorporate into position descriptions to attract adaptive employees? (You can even copy and paste qualification language from the tool into scopes of work!) Which interview questions should I ask to screen for adaptive employee competencies? (You can copy and paste interview questions into your screening, interview, and reference check protocols!) Has the tool been tested? Yes, staff within USAID’s Global Development Lab and on the USAID LEARN contract tested the tool, providing feedback on the minimum viable product and subsequent versions. Testers confirmed finding the tool useful, and gave it a 9/10 score when asked if they would recommend it to colleagues. Some specific feedback from testers included: "The tool prompts deeper thought on what you might need and want in a job candidate" and "All [of the interview questions I used from the tool] worked well." What about the existing staff? How can they gain greater skills in adaptive management? Existing USAID staff and implementing partners can access online training in collaborating, learning, and adapting (CLA) and find resources in the CLA Toolkit. USAID staff also have access to an internal CLA community of practice and five-day, in-person CLA training.

Evidence Base for Collaborating, Learning, and Adapting: summary of the literature review (2016.08) - Learning Lab (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Adaptive leadership in the coronavirus response - Ramalingam, Ben; Wild, Leni; Ferrari, Matt (ODI, 2020)
The coronavirus pandemic poses unprecedented challenges to science, policy and the interface between the two. How – and how quickly – policy-makers, practitioners and researchers react to this emerging and complex crisis is making a profound difference to people’s lives and livelihoods (WHO, 2020). But how can we ensure effective collective decision-making on the basis of emerging evidence, changing trends and shifting scientific understanding, all in the face of considerable uncertainty? Recent experience highlights the need for adaptive leadership in national and global responses to the outbreak. This briefing paper sets out key principles for what this might look like, and proposes a roadmap for policy-makers, practitioners and researchers to move towards such an approach as they tackle the unfolding crisis. Key messages Tackling the coronavirus outbreak requires adaptation at operational and leadership levels. Operationally, there is scope to strengthen evidence-based adaptive management practices, to adjust the mix and type of interventions being implemented and learn as we go so as to achieve shared goals. This requires adaptive leadership capacities, being open and transparent about learning, using collective decision-making processes and building trust with communities and individuals.

All about behaviour: KAPE, Adaptation and ' Sticky' Institutional Change - Power, Greg (Global Partners Governance, 2016)
This paper describes Global Partners Governance’s (GPG’s) approach to institutional reform and political change. Developed over the last decade of working in some of the most complex and sensitive political environments with politicians and officials in parliaments, political parties, ministries and local government, it describes the KAPE® (knowledge-application-practice-effect) methodology that we adopt to get ‘sticky’ institutional and behavioural change. Contents 1) Two dimensions of ‘adaptive programmes’: Flexible delivery and getting behaviour change 2) Enabling Change: KAPE and The Logic of Institutional Reform (Knowledge-Application-Practice-Effect) - K: Knowledge – Defining the problem and what to do about it - A: Application – Making Systems Work in Practice - P: Practice – Pockets of good practice and establishing ‘the new normal’ - E: Effect – Improved performance and the ‘Ripple Effect’ 3) Measuring Impact: Monitoring and Evolving 4) Conclusion: Behavioural insights, adaptive management and sticky change

Learning and adaptation: 6 pitfalls to avoid - Valters, Craig (Devex, 2016)

Try, learn, adapt, repeat: T/A Learn reflections - Alan (www.globalintegrity.org, 2015)
By Alan Hudson — November 16, 2015. I spent last week in Rio de Janeiro (tough assignment, I know), participating in the Transparency and Accountability Initiative’s third T/A Learn Annual Workshop. As the report of the second Annual Workshop, held...

Adaptive Leadership: Accelerating Enterprise Agility - Highsmith, Jim (Addison-Wesley Professional., 2013)

Complexity Leadership Theory: An Interactive Perspective on Leading in Complex Adaptive Systems - Lichtenstein, Uhl-Bien; Schreiber, Orton; Lichtenstein, Benyamin; Uhl-Bien, Mary; Marion, Russ; Seers, Anson; Orton, James Douglas; Schreiber, Craig (Emergence, 2006)
Traditional, hierarchical views of leadership are less and less useful given the complexities of our modern world. Leadership theory must transition to new perspec-tives that account for the complex adaptive needs of organizations. In this paper, we propose that leadership (as opposed to leaders) can be seen as a complex dynamic process that emerges in the interactive "spaces between" people and ideas. That is, leadership is a dynamic that transcends the capabilities of individuals alone; it is the product of interaction, tension, and exchange rules governing changes in per-ceptions and understanding. We label this a dynamic of adaptive leadership, and we show how this dynamic provides important insights about the nature of leadership and its outcomes in organizational fields. We define a leadership event as a perceived segment of action whose meaning is created by the interactions of actors involved in producing it, and we present a set of innovative methods for capturing and analyzing these contextually driven processes. We provide theoretical and practical implications of these ideas for organizational behavior and organization and management theory.

Navigating adaptive approaches for development programmes - Pett, Jamie (ODI, 2020)
This working paper compares six of the most prominent adaptive approaches to emerge over the past two decades. Three come from the world of innovation, largely in the private sector (agile, lean startup and human-centred design), and three from the global development sector (thinking and working politically, forms of adaptive management and problem-driven iterative adaptation). While all of these approaches are valuable when used in the right context, practitioners may be perplexed by the multiplicity of methods and jargon. This paper aims to address some of this confusion by mapping where these approaches have come from and showing how they can be applied across the adaptive programme cycle. Armed with this knowledge, practitioners might experiment with different combinations and sequences of adaptive approaches according to the kind of problem and context faced. In turn, this may help us move beyond a siloed view of approaches linked to innovation, adaptive management or more politically smart ways of working. Key messages: • Adaptive approaches have emerged in several sectors, including software development, product and service design, technology startups and international development. • Adaptive approaches can help practitioners counteract misplaced certainty. By talking to potential users, understanding institutions, interests and ideas and investigating the root causes of a problem, practitioners applying these approaches can illuminate the underlying nature of the problem and context. • Rather than building a whole solution straight away, these approaches commonly encourage practitioners to start small and use structured cycles of testing and learning. There is scope to further consider how different approaches can be better brought together and combined. • Adaptive approaches in development provide a wider range of options for what to create and facilitate – not only products or services, but also forms of collective action. There are also alternative ways to think about scale – considering how others might take up an idea and looking for leverage, rather than quantity.

Adapting development: improving services to the poor - Wild, Leni; Booth, David; Cummings, Clare; Foresti, Marta; Wales, Joseph (ODI, 2015)
On current trends, it will take decades or longer to bring basic services to the world’s most disadvantaged people. Meeting this challenge means recognising the political conditions that enable or obstruct development progress - a radical departure from the approach of the Millennium Development Goals.
Keywords: Practice

Complexity, Adaptation, and Results - Barder, Owen; Ramalingam, Ben (Center For Global Development, 2012)
In the last of a series of three blog posts looking at the implications of complexity theory for development, Owen Barder and Ben Ramalingam look at the implications of complexity for the trend towards results-based management in development cooperation. They argue that is a common mistake to see a contradiction between recognising complexity and focusing on results: on the contrary, complexity provides a powerful reason for pursuing the results agenda, but it has to be done in ways which reflect the context. In the 2012 Kapuscinski lecture Owen argued that economic and political systems can best be thought of as complex adaptive systems, and that development should be understood as an emergent property of those systems. As explained in detail in Ben’s forthcoming book, these interactive systems are made up of adaptive actors, whose actions are a self-organised search for fitness on a shifting landscape. Systems like this undergo change in dynamic, non-linear ways; characterised by explosive surprises and tipping points as well as periods of relative stability. If development arises from the interactions of a dynamic and unpredictable system, you might draw the conclusion that it makes no sense to try to assess or measure the results of particular development interventions. That would be the wrong conclusion to reach. While the complexity of development implies a different way of thinking about evaluation, accountability and results, it also means that the ‘results agenda’ is more important than ever.
Keywords: IMPORTANT

The Strategy Testing Workbook: Politically-Smart Adaptive Programming in Complex Environments - Nixon, Nicola; O'Donnell, Carolyn; Rajalingam, Gobie; Tweedie, Pauline; Sullivan, Elizabeth (The Asia Foundation, 2024)
The guide begins with a section on what we at TAF have learned about practicing Strategy Testing, highlighting things that we didn’t know when we started out. Some of these lessons may seem obvious, but others may strike you as less so. In any case, we believe that, when taken together, they provide a useful reminder of some of the pitfalls that arise in efforts to practice Adaptive Management. Moreover, they help to remind us that there are multiple layers to doing Strategy Testing effectively as a system instead of reducing it to its component parts and applying them mechanistically. Thus these lessons are useful to read now and to revisit later. The guide then comprises three more sections: • Part 1, the Design Stage, involves constructing the system and making sure everyone is on board; • Part 2, the Inception Phase (start-up phase), helps the implementing team to make the leap from the ideal initially set out in the design stage to the grounding, support, and frameworks that the team will need to implement Strategy Testing in a meaningful and impactful way. We’ve found that the gap between design and implementation is very often the cause of an ineffective ‘all talk and no walk’ approach to Adaptive Management. And finally; • Part 3 covers Program Implementation – the practices, knowledge, and culture needed for the feedback loop that underpins Strategy Testing. The guide can be used for individual or group learning, or it can be used directly to inform Reflection Sessions (see Section 3) through the questions we raise or the activities herein.

Adaptive Management - Jenal, Marcus; Cunningham, Shawn (Annual Reflection 2019, 2019)

Delivering institutional reform at scale: Problem-driven approaches supported by adaptive programming - Manuel, Clare (DFID-LASER Programme, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others). Second synthesis paper - Delivering institutional reform at scale: problem-driven approaches supported by adaptive programming February 2016 Drawing on our experience on the ground, this peer-reviewed paper suggests how problem driven approaches, supported by adaptive programme management can be implemented at scale in relation to donor programming aimed at institutional reform and improving state capability.
Keywords: IMPORTANT

Adaptive management: why we find it so hard to operationalise - Teskey, Graham (Abt Associates - Governance Soapbox, 2018)

Summer school on Adaptive Management - 2019 - CID (2019)
General description of the curriculum

Making Good Use of Adaptive Management - Doremus, Holly; Andreen, William L.; Camacho, Alejandro E.; Farber, Daniel A.; Glicksman, Robert L.; Goble, Dale D.; Karkkainen, Bradley C.; Rohlf, Dan; Tarlock, A. Dan; Zellmer, Sandra B.; Jones, Shana Campbell; Huang, Yee (Center for Progressive Reform, 2011)

Bridging Real-Time Data and Adaptive Management in International Devepment - Case Study Report - Ramalingam, Ben; Barnett, Inka; Valters, Craig; Oppenheimer, Carrie; Levy, Anna; Hernandez, Kevin (IDS, 2017)

A top Toolkit on Adaptive Management. But is that a good idea? – FP2P - Green, Duncan (From Poverty to Power, 2021)

Building a global learning alliance on adaptive management - Wild, Leni; Ramalingam, Ben (ODI, 2018)

Adaptive management: an overview of the concept and its practical application in the Scottish context - Blackstock, Kirsty; Brown, Katrina; Gimona, Alessandro; Prager, Katrin; Irvine, Justin (The James Hutton Institute, 2016)

How to do Adaptive Management in 15 easy steps – from a top new toolkit – FP2P - Green, Duncan (From Poverty to Power, 2021)

Adaptive Management: Responding to the evolving needs of PRIME's complex systems - Picon, Diana; Wild, Lorenz (Mercy Corps, 2015)

The road to adaptive management: knowledge, leadership, culture and rules - Byrne, Karri Goeldner; Sparkman, Timothy; Fowler, Ben (The BEAM Exchange, 2016)
Keywords: IMPORTANT; Practice

Short Course - Adaptive Management, an overview - Bazaz Smith, Komal (American University, 2019)

Second (and Third) Thoughts on Adaptive Management and Thinking and Working Politically - Green, Duncan (From Poverty to Power, 2022)
Self-Critical reflections on AM and TWP. Linking it with The Hype Cycle - "it feels like we are heading downward to the ‘trough of disillusionment’ form the initial peak of ‘inflated expectations’, but we will bounce back to something more sustained, that becomes a permanent feature of the aid landscape".

The Difference Learning Makes - Factors that enable and inhibit adaptive programming - Gray, Stephen; Carl, Andy (Christian Aid, 2022)
Executive Summary When Christian Aid (CA) Ireland devised its multi-country and multi-year Irish Aid funded Programme Grant II (2017-2022), they opted to move away from a linear programme management approach and to explore an adaptive one. Across seven countries: Angola, Colombia, El Salvador, Guatemala, Israel and the occupied Palestinian territory, Sierra Leone, and Zimbabwe, CA and partner organisations support marginalised communities to realise their rights, reduce violence and address gender inequality. Since 2019, Adapt Peacebuilding has accompanied CA Ireland, CA country teams and partner organisations as they experimented with using a deliberate adaptive approach. The authors were also asked to follow up on an initial study by CA Ireland and Overseas Development Institute in 2018, which described the rationale for adopting this new approach and included early lessons from its first year of implementation. The aim of this study is to help deepen CA Ireland, CA country teams’ and partners’ understanding of (a) whether their application of adaptive programming has resulted in better development outcomes, and (b) how they can better understand the factors that enabled or inhibited the effectiveness of using this approach. Over the past three years, this study has found evidence and multiple examples that show adaptive programming contributed to better development outcomes. The main reasons cited were that these were made possible both from improvements to programming strategies based on proactive reflection and learning, as well as those that stem from the reactive capacity of adaptive programmes to change course in response to unanticipated changes in operating conditions. This study found that adaptive programming has enabled better development practice where organisations are enhancing their skills to better respond and be flexible to contextual challenges. 72% of partners surveyed described adaptive programming as the most useful approach to programme management that they have used. The programme approach has meant that CA and partner staff were better able to explore the significance of change in the context and their contributions to them. It also enabled spaces for meaningful engagement with communities in learning and programme planning processes and encouraged opportunities for experimentation in programming. The study also found that adaptive programming has supported flexible delivery. This led to better outcomes that would not have been possible were the programme not able to make flexible adjustments. The main focus has been the analysis of nine factors that can determine the effectiveness and impact (or otherwise) of using an adaptive approach, flagging important issues for understanding. These factors are identified as: 1) Leadership; 2) Organisational culture; 3) Conceptual understanding; 4) Staff capacities; 5) Partnership approaches; 6) Participation; 7) Methods and tools; 8) Administrative procedures; and 9) The operating context. Together these can provide an analytical framework for assessing an organisation’s ‘adaptive scope’, which can be used as a tool for better understanding an organisation’s potential to generate improved development outcomes via adaptive programming and how to strengthen them. The study concludes with several recommendations for CA Ireland, all of which have relevance for a broader community of donors and implementing organisations interested in the potential of adaptive programming.

Learning to adapt & adapting to learn - Using elements of outcome mapping in the ‘Resilient Adolescents in the Syria Crisis’ programme - van Ongevalle, Jan; Kvintradze, Ana; Rennesson, Gaël; Miller, David (Save the Children, 2021)
This learning paper highlights how elements of outcome mapping were used by Save the Children Sweden in a project (2018-2020) that supports adolescents, affected by the Syria crisis, to become more resilient. The paper first outlines how the spheres of influence framework has been applied to develop an actor focused theory of change. It then describes how progress markers, as an alternative to SMART indicators, were formulated to monitor the programme’s results. The paper also outlines how long lists of progress markers were categorised in a more realistic and practical results framework. The paper then continues to elaborate how outcome journals, qualitative data analysis techniques and regular review meetings and reflection workshops were utilised for data collection, for collective learning among programme stakeholders and for informing planning and programme adjustment. Various practical guidelines and tips on how to implement elements of outcome mapping are provided. The final part of the paper explores to what extent outcome mapping was able to foster several key enablers of adaptive programme management and highlights some of the challenges that programme stakeholders faced. Practical recommendations towards the use of outcome mapping in future programmes are also proposed.

When Complex is as Simple as it Gets: Guide for Recasting Policy and Management in the Anthropocene - Roe, Emery (Institute for Development Studies, 2023)
Many readers recognise and understand that complex is about as simple as it gets for major policy and management. This guide is for those unwilling in the Anthropocene to shrink back into the older platitudes about ‘keep it simple’ and ‘not to worry, we’ll scale up the analysis later on’. This guide offers key concepts, methods, counternarratives, and analogies that recast major policy and management issues in ways that do not deny their complexity but help render them more tractable for action.
Accepted: 2023-06-06T09:51:20Z

Summer School Course - Adaptive Management - Working Effectively in the Complexity of International Development (weekplan) - Green, Duncan; Guijt, Irene (Oxfam, 2018)

Adaptive management: What it means for CSOs - O’Donnell, Michael (Bond, 2016)
Keywords: IMPORTANT

How to set up and manage an adaptive programme - Lessons from the Action on Climate Today (ACT) Programme - Cooke, Katherine (OPM, 2017)

DFID’s approach to value for money in programme and portfolio management - ICAI (Independent Commission for Aid Impact (ICAI), 2018)
ICAI published this review on DFID’s approach to value for money in February 2018, and as value for money is both a process and an outcome and cuts across all aspects of DFID’s operations, did not score this review. We made five recommendations and published a follow-up to this review in July 2019. All UK government departments are required to achieve value for money in their use of public funds. In recent years, DFID has been working to build value for money considerations further into its management processes and its relationships with implementers and multilateral partners, establishing itself as a global champion on value for money. Review This review was published in February. Though it was not rated, ICAI made five recommendations, and found that the Department for International Development’s approach to value for money was helping to make UK aid spending go further, but improvements are still needed. Findings This review found that DFID has strengthened its processes and systems for ensuring it gains maximum value for each pound spent, has taken swift remedial action to tackle under-performing programmes, and has become a strong global champion on value for money. The review also found that DFID has been diligent in its efforts to cut waste, detect fraud, and improve efficiency, and that this work is improving the return on the UK investment in aid. However, the review found that DFID’s approach was not adequately reporting and capturing results and value for money at the country portfolio level, or how programmes work together to deliver lasting impact, including reducing future dependency on aid. It also found that weakness in the annual review process could undermine DFID’s approach to value for money. It found that targets were frequently revised, and that there could be pressures for optimistic scoring of programmes. Recommendations Based on this review, we made the following five recommendations to help DFID improve its approach to value for money still further: DFID country offices should articulate cross-cutting value for money objectives at the country portfolio level, and should report periodically on progress at that level. Drawing on its experience with introducing adaptive programming, DFID should encourage programmes to experiment with different ways of delivering results more cost-effectively, particularly for more complex programming. DFID should ensure that principles of development effectiveness – such as ensuring partner country leadership, building national capacity and empowering beneficiaries – are more explicit in its value for money approach. Programmes should reflect these principles in their value for money frameworks, and where appropriate incorporate qualitative indicators of progress at that level. DFID should be more explicit about the assumptions underlying the economic case in its business cases, and ensure that these are taken into account in programme monitoring. Delivery plans should specify points in the programme cycle when the economic case should be fully reassessed. Senior responsible owners should also determine whether a reassessment is needed following material changes in the programme, results targets or context. Annual review scores should include an assessment of whether programmes are likely to achieve their intended outcomes in a cost-effective way. DFID should consider introducing further quality assurance into the setting and adjustment of logframe targets.

Building a team culture for Adaptive Management in MSD: 5 Strategies MEL Managers Say Work - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (USAID, 2023)
Keywords: Bolder Meghan; Gover Dun; Henao Lina; Nasution Zulka; Okutu David

Context-monitoring for adaptive management - Pickwick, Sarah (World Vision, 2022)

Adaptive Learning Guide: A pathway to stronger collaboration, learning, and adapting - Ross, Joey; Karlage, James; Etheridge, James; Alade, Mayowa; Fifield, Jocelyn; Goodwin, Christian; Semrau, Katherine; Hirschhorn, Lisa (USAID MOMENTUM Knowledge Accelerator, 2021)
The purpose of this Adaptive Learning Guide is to provide MOMENTUM project teams with the information and resources to integrate adaptive learning into the design, implementation, and improvement of MNCH/FP/RH programs. This guide provides a conceptual introduction to adaptive learning using links to existing resources and real-world examples of how adaptive learning can drive continuous learning and improvement in project work. The guide is built upon three foundational assumptions: We work in dynamic, often unpredictable environments. Unexpected turns of events will occur. Progress is rarely, if ever, linear. Integrating the principles and practices of USAID’s Collaborating, Learning, and Adapting Toolkit into projects and initiatives requires designing for learning and adaptation. We intend the guide to serve as a “starting point” for interested individuals and teams to begin or strengthen the processes that support the integration of adaptive learning into project work.

SAVI Approach Paper 14: Learning, Adaptation and Communications - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme, aiming to put learning and adaptation at the centre of all decision-making. Learning and adaptation takes place in SAVI at three levels: the work of partners; the work of SAVI delivery teams; and the enabling environment of the programme as a whole. Achieving...

Thoughts on the use of hypotheses in adaptive management - Sparkman, Timothy (BEAM Exchange, 2015)
New insights, opinions and perspectives on market systems development, from experts and practitioners.

Policy experimentation and innovation as a response to complexity in China’s management of health reforms - Husain, Lewis (Globalization and Health, 2017)
There are increasing criticisms of dominant models for scaling up health systems in developing countries and a recognition that approaches are needed that better take into account the complexity of health interventions. Since Reform and Opening in the late 1970s, Chinese government has managed complex, rapid and intersecting reforms across many policy areas. As with reforms in other policy areas, reform of the health system has been through a process of trial and error. There is increasing understanding of the importance of policy experimentation and innovation in many of China’s reforms; this article argues that these processes have been important in rebuilding China’s health system. While China’s current system still has many problems, progress is being made in developing a functioning system able to ensure broad population access. The article analyses Chinese thinking on policy experimentation and innovation and their use in management of complex reforms. It argues that China’s management of reform allows space for policy tailoring and innovation by sub-national governments under a broad agreement over the ends of reform, and that shared understandings of policy innovation, alongside informational infrastructures for the systemic propagation and codification of useful practices, provide a framework for managing change in complex environments and under conditions of uncertainty in which ‘what works’ is not knowable in advance. The article situates China’s use of experimentation and innovation in management of health system reform in relation to recent literature which applies complex systems thinking to global health, and concludes that there are lessons to be learnt from China’s approaches to managing complexity in development of health systems for the benefit of the poor.

Contracts for adaptive programming - Bryan, Kevin; Carter, Paddy (ODI, 2016)
Adaptive programming is an approach to development that encourages experimentation, learning & adaptation. This report examines the contractual underpinnings of this approach.

edX MOOC: Adaptive Leadership in Development - edX (edX, 2016)
Gain the skills to be an adaptive leader in development and learn how to uncover local solutions to complex problems in developing countries.

Scrambling after Moving Targets: Monitoring & Evaluation Applied to Adaptive Management Approaches in Peacebuilding - Woodrow, Peter; Jean, Isabella (New Directions in Peacebuilding Evaluation, 2019)
In this landmark collection, the voices of pathMakers and innovators in peacebuilding evaluation are assembled to provide new direction for the field.
Keywords: IMPORTANT

Mainsreaming gender in an adaptive, politically smart governance programme - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
• This paper looks at the experience of gender mainstreaming in the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • When development programmes try to engage with political stakeholders and align with the priorities of wider coalitions there is a danger that gender equality is de-prioritised. • It is important that formal political economy analysis, as well as other data collection, analysis and consultation exercises, are gender-sensitive. Teams should also look for ways to make gendered political and power analysis part of the everyday routine practice of staff. • Working politically and adaptively to advance gender objectives calls for staff with a specific skillset, as well as links to appropriate networks and political stakeholders. It also implies establishing checks and incentives to hold staff and partners accountable for gender objectives, and strong and consistent messaging from team leaders.

How adaptive M&E from the peace sector can help demonstrate the value of aid - Kratzer, Sebastian (2023)
Over the last decade, the peace sector has been developing and adapting Monitoring and Evaluation (M&E) systems and tools to fit their contexts and ways of working. This evolution may hold some insights for the aid community in how to go beyond more traditional, backwards-looking M&E to navigate today’s volatile, interest-based world of politics and aid.

Program Cycle - Discussion Note: Designing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Rethinking value for money for adaptive, politically smart programmes - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
- This short paper draws out lessons for working effectively with and through partners, based on the experience of the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • Cultivating effective partnerships can be a key part of delivering locally legitimate projects that have the potential to create sustainable change. Adaptive and politically informed ways of working create specific opportunities and challenges for doing this well. • Flexible and adaptive programmes are deliberately designed to experiment and to make small investments in different areas, to see what will work. While this is often important for making headway on complex challenges, it can also leave partners exposed and can undermine trust. • It can also be challenging to balance the need to meet accountability commitments to donors while allowing local partners to take the lead in pursuing their own objectives. • Co-creating plans, priorities and activities with partners has the potential to resolve some of these tensions. But the time and patience required to do this successfully should not be underestimated, and can be difficult to maintain in the face of pressure from donors to see results within a confined timeframe.

Examining the results and adaptation ideas in foreign aid - Janus, Heiner (University of Manchester, 2020)
This thesis applies ideational and institutional theories to analyse how two specific ideas, results and adaptation, have changed the theory and practice of development cooperation. The thesis addresses the question of why the results and adaptation ideas are often treated as binaries and how this debate has evolved historically. In a first theoretical paper, the evolution of results and adaptation is conceptualised as a combination of institutional layering and diffusion within development organisations. The second theoretical paper applies ideational theory, in particular, the coalition magnet framework, to China as a donor country. The empirical papers apply ideational and institutional theories to study aid projects funded by the World Bank and China in the Rwandan agriculture sector. The third paper analyses through which mechanism, results-based principal-agent relationships or problem-driven iterative adaptation, the World Bankâs Program for Results in the agriculture sector in Rwanda has led to increased agricultural productivity. The paper combines causal process tracing and contribution analysis to investigate two underlying theories of change of the Program for Results. The fourth paper applies the same framework and methodology to the Chinese Agricultural Technology Demonstration Center in Rwanda. The fifth paper compares both projects, the World Bank project and the Chinese project. The thesis finds that the ideas of results and adaptation are often presented as mutually exclusive mainly at the general level of public philosophies or paradigms, but show overlap and potential for integration on the level of framing policy problems and policy solutions. The thesis also demonstrates that there is unexplored potential for convergence between China and Development Assistance Committee donors around âcoalition magnetâ ideas. The empirical part of the thesis reveals how results-based and adaptive causal mechanisms co-exist within given aid interventions by the World Bank and China, how these interact and how they ultimately contribute to achieving development outcomes. The key finding is that the broader political context of the Rwandan agricultural sector is the main factor for determining development outcomes, which neither the World Bank project nor the Chinese projects take into account. The comparison of the World Bankâs and Chinaâs interventions finds that donor organisations need to address how results-based ideas in combination adaptive development ideas can be better tailored to fit into the specific context of the Rwandan agriculture sector.

Towards an Alternative Development Management Paradigm? - Shutt, Cathy (Expertgruppen för biståndsanalys (EBA), 2016)
Demonstrating results has been a concern in international development cooperation ever since it was started and in recent years there has been an increased focus on achieving and reporting on “results”. Despite the fact that everyone involved in development cooperation wants to make a difference there has been a growing criticism from practitioners about the “results agenda” based on a concern that the approaches used are not fit for purpose. In the EBA-report, Cathy Shutt, at the University of Sussex, scrutinizes the recent critical debate about results based management, and the main arguments and motives behind the criticism. She shows that the debate is not only a matter of obsessive measurement and reporting of meaningless numbers for political accountability, but also a matter of problematic assumptions and how we think about development, evidence and learning. In the report, Shutt also explores what could be learned from those who are not just critiquing results based management approaches but also proposing alternatives. Are these new alternatives an answer to the criticism?
Keywords: IMPORTANT

“Everyone is talking about it, but no one is doing it”: How implementation research is – or isn’t – informing adaptation towards scale in international education - Dowd, Amy Jo (International Journal of Educational Development, 2024)
With growing evidence of what works in education, governments and their partners strive towards scale. While implementation research to adapt solutions holds promise for testing what works, where and for whom, its use in education is limited. Sixty-three international education stakeholders from government, academia, think tanks, local and international non-governmental organizations, multi- and bi-laterals and foundations offer insight into three modes of implementation research that differ on responsiveness, timeliness and stakeholder collaboration. They speak to the primacy of government involvement, trust and curiosity in collaborative efforts. This study explores enabling factors for evidence-based implementation improvement on the pathway to scale.
Keywords: Evidence-based practice; Implementation research; International education

Navigation by Judgment: Why and when Top Down Management of Foreign Aid Doesn't Work - Honig, Dan (Oxford University Press, 2018)
Foreign aid organizations collectively spend hundreds of billions of dollars annually, with mixed results. Part of the problem in these endeavors lies in their execution. When should foreign aid organizations empower actors on the front lines of delivery to guide aid interventions, and when should distant headquarters lead? In Navigation by Judgment, Dan Honig argues that high-quality implementation of foreign aid programs often requires contextual information that cannot be seen by those in distant headquarters. Tight controls and a focus on reaching pre-set measurable targets often prevent front-line workers from using skill, local knowledge, and creativity to solve problems in ways that maximize the impact of foreign aid. Drawing on a novel database of over 14,000 discrete development projects across nine aid agencies and eight paired case studies of development projects, Honig concludes that aid agencies will often benefit from giving field agents the authority to use their own judgments to guide aid delivery. This "navigation by judgment" is particularly valuable when environments are unpredictable and when accomplishing an aid program's goals is hard to accurately measure. Highlighting a crucial obstacle for effective global aid, Navigation by Judgment shows that the management of aid projects matters for aid effectiveness.
Google-Books-ID: GT5MDwAAQBAJ

Using adaptive development to support feminist action - O’Neil, Tam (ODI, 2016)
This paper looks at how adaptive development is being applied by gender programmes and argues that gender and adaptive development communities have much to offer each other.

DRG Center practical tips to implement more context-adaptive programming - Jacobstein, David (#AdaptDev, 2018)
Hi #adaptdevers, The cross-sectoral programs team in the DRG Center have been working in support of ways that programming can be made more aware of, and responsive to, context considerations that have to do with incentives and relationships between different actors - often called power dynamics or political economy. Following several discussions with field folks, we were asked to come up with simple and practical tips that could help staff to implement more context-adaptive programming, or to better Work Politically to use TWP jargon. With assistance from many of our field staff and partners, we've put together three documents (to start) that have now been cleared to share publicly: • Tips on Making Your Solicitations Invite Context-Driven Adaptive Programming - suggestions spanning most sections of a typical solicitation to better weave in Thinking and Working Politically. I'm particularly excited that this document contains embedded links to excerpts from a set of solicitations that model good practice. You can also find a summary of all the excerpts from real solicitations, and links onward to the public posting of those solicitations on Fed Biz Ops or Grants.gov, here. • Tips on Power Dynamics and Theories of Change - suggestions relevant to those working on project designs and logic models. • Tips for Better Use of Advisory Councils - suggestions to set up better advisory bodies that help you to incorporate political economy more automatically into your programmatic adjustments. I hope that you'll find these practical and helpful! Feedback is always welcome. Best, David

Working effectively through partnerships - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
• This paper looks critically at the approach to value for money (VfM) in the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • Adaptive, politically smart programmes like I4ID aim to deliver VfM by learning about what will work in complex environments, and quickly incorporating those lessons into delivery. When functioning properly, they can rapidly wind down activities as new information emerges and divert funding to more effective alternatives. • This means that adaptive programmes will achieve their potential to deliver strong VfM when their processes are good – when appraisal of experimental efforts is timely, consistent, knowledgeable and politically astute. As these programmes mature in their implementation phase, VfM evaluation should be focused on checking for a culture of adaptation and learning supported by strong adaptive processes. • While economy is important for adaptive programmes, it is also important that keeping costs low does not deprive teams of the resources, staff, and management and administration time they need to gather information, experiment, learn and adapt.

Evaluation and learning in complex, rapidly changing health systems: China’s management of health sector reform - Xiao, Yue; Husain, Lewis; Bloom, Gerald (Globalization and Health, 2018)
Healthcare systems are increasingly recognised as complex, in which a range of non-linear and emergent behaviours occur. China’s healthcare system is no exception. The hugeness of China, and the variation in conditions in different jurisdictions present very substantial challenges to reformers, and militate against adopting one-size-fits-all policy solutions. As a consequence, approaches to change management in China have frequently emphasised the importance of sub-national experimentation, innovation, and learning. Multiple mechanisms exist within the government structure to allow and encourage flexible implementation of policies, and tailoring of reforms to context. These limit the risk of large-scale policy failures and play a role in exploring new reform directions and potentially systemically-useful practices. They have helped in managing the huge transition that China has undergone from the 1970s onwards. China has historically made use of a number of mechanisms to encourage learning from innovative and emergent policy practices. Policy evaluation is increasingly becoming a tool used to probe emergent practices and inform iterative policy making/refining. This paper examines the case of a central policy research institute whose mandate includes evaluating reforms and providing feedback to the health ministry. Evaluation approaches being used are evolving as Chinese research agencies become increasingly professionalised, and in response to the increasing complexity of reforms. The paper argues that learning from widespread innovation and experimentation is challenging, but necessary for stewardship of large, and rapidly-changing systems.

Interview protocol: Most significant turning points - Prieto Martin, Pedro; Faith, Becky (Institute of Development Studies, 2017)
This interview protocol was used for a research project on adaptiveness in technology for governance initiatives in Kenya. For more information, please read the research report at: Prieto Martin, P.; Hernandez, K.; Faith, B. and Ramalingam, B. (2017) Doing Digital Development Differently: Lessons in adaptive management from technology for governance initiatives in Kenya, MAVC Research Report, Brighton: Institute of Development Studies, ids.ac.uk/project/making-all-voices-count
Keywords: IMPORTANT

How DFID can better manage complexity in development programming - Sharp, Samuel; Valters, Craig; Whitty, Brendan (ODI, 2019)
The United Kingdom’s (UK) Department for International Development (DFID) is an ambitious government department that is committed to reducing poverty and conflict overseas. Many of the issues on which DFID works are complex; whether focused on climate change, gender equality, health or other priorities, simple solutions rarely exist. And to tackle these complex challenges, DFID staff must interact with unpredictable systems of political, organisational and individual behaviours and incentives. There is a risk that complex problems spur more complicated programmes; that the complexity of development challenges is addressed through designing programmes with too many projects and implementers. While there may be valid reasons for this, too many of these complicated programmes will overburden staff. This briefing note is the outcome of an ongoing process within DFID to confront these issues and answer the question: how can DFID design and manage programmes to address complex development challenges without creating too much staff workload? Key messages DFID deals with complex problems, which require flexible systems to support testing, learning and adaptation. • Complex problems do not necessarily require workload-heavy delivery structures, but simpler approaches depend on delivery partners’ experience and competence. • However, programmes that tackle complex problems do require more hands-on engagement and face more workload from inflexible compliance requirements. We suggest that DFID and similar agencies: • Pay closer attention to delivery options in programme design, making use of existing options where possible and, where not, fostering local organisations through long-term investments. • Encourage programme designers to articulate how ambition matches resources and consider ‘good enough’ design. • Reduce the burden of compliance by cultivating partner autonomy, reassessing results and valuefor-money requirements and promoting more flexible contracting and procurement. • Plan and prioritise management resources across a portfolio of programmes to make sure they can be focused in the right areas, where the complexity of the problem requires greater engagement.

Transforming M&E for Uncertain and Complex Contexts: The UNDP’s Innovation Sandbox Approach - Fraser, Dugan; Haldrup, Søren (Powered by Evidence Podcast, 2022)
How can we transform monitoring and evaluation (M&E) into a more adaptive, emergent process to address uncertainty and complexity in todays’ world? How do we move from compliance and accountability to learning – to support better, more timely, decisions? Join GEI Program Manager, Dugan Fraser, as he discusses these questions and others with Special Guest, Søren Haldrup, from UNDP's Strategic Innovation Unit where he manages UNDP's innovation facility and leads a new initiative called the M&E Sandbox.

Timely evaluation in international development - Webster, Jayne; Exley, Josephine; Copestake, James; Davies, Rick; Hargreaves, James (Journal of Development Effectiveness, 2018)
Impact and process evaluations are increasingly used in international development; however they are generally retrospective in outlook. A more timely approach to evaluation aims to identify necessary, feasible and effective changes during a programme or intervention’s lifetime. This paper aims to identify, categorise, describe and critically appraise methods to support more timely evaluation in international development. Potential methods were identified through scoping seminar, public symposium, targeted review of the literature, and the authors’ own experiences and opinions. Findings from the different data sources were reviewed collectively by the author group and triangulated to develop an analytical framework. We identified four purposes of timely evaluation for international development, and critiqued the use of approaches against four dimensions of timeliness and flexibility. Whilst we found significant interest in more timely approaches to evaluation in international development, there was a dearth of published empirical evidence upon which to base strong recommendations. There is significant potential for timely evaluation to improve international development outcomes. New approaches to mixing and adapting existing methods, together with new technologies offer increased potential. Research is needed to provide an empirical evidence base upon which to further develop the application, across sectors and contexts, of timely evaluation in international development.
Keywords: Adaptive learning; Outcome evaluation; Programme improvement; impact evaluation

Systems-aware social accountability: Harnessing Practitioner Insights for More Responsive Governance - Guerzovich, Florencia (Pact, 2023)
The framework’s four principles, described below, are not exclusive to social accountability interventions; for example, Pact has published tools on how to use political economy analysis or integrate adaptive management principles into programming. Rather, the principles highlight how – by including the right combination of mindsets, management approaches, analytic approaches and tools – practitioners can develop and apply a deep understanding of a system to improve relationships within it, in support of greater accountability and improved service delivery. - Use a Holistic Lens - Recognize that there is always a system; understand and engage with it​: Developing a strong understanding of the system in which a project works and effectively integrating this knowledge into implementation increases the chances that local actors will sustain the interventions. - Right Fit the Approach​ - Equipped with a holistic understanding of the context, teams identify where they have a comparative advantage in a specific system. In other words, they identify where their resources, expertise and partners have the greatest potential for impact, then set realistic targets that they revise periodically. -Orchestrate Across The System -​ Practitioners take a networked, rather than a top-down, approach to capitalize on their convening power and maximize opportunity to facilitate the most-promising alignments across and within their projects, portfolios and systems. Orchestrators use their individual power, relationships and insight into the local system to enable, not impose, promising interactions and mitigate the risks of damaging ones. - Manage Adaptively - Monitor, evaluate and reflect on emerging patterns of data, evidence and learning to inform decision-making within and, equally importantly, across project cycles. Where possible, practitioners should consider how to use short-term projects to play a long-term game by linking new projects to the lessons and results of their predecessors and ensuring that they are responsive to the evolving context, particularly opportunities, limits and risks.

Adaptive Evaluation: A Complexity-based approach to Systematic Learning for Innovation and Scaling in Development - Gokhale, Siddhant; Walton, Michael (Center for International Development, Harvard University, 2023)
Nearly all challenges in international development tend to be complex because they depend on constantly evolving human behaviour, systems, and contexts, involving multiple actors, entities, and processes. As a result, both the discovery and scaling of innovations to address challenges in development often involve changes in system behaviour or even system-level transformation. This is rarely a linear process over time and can result in unexpected outcomes. Existing evaluation techniques commonly used in international development, including Randomized Control Trials (RCT) and quasi-experimental methods, are good at assessing specific effects of interventions but are not designed for the change processes inherent to innovation and scaling within a system. There is a need to reconstruct how we use existing measurement tools, techniques, and methodologies so that they capture the complexity of the environment in which an intervention or change occurs. We introduce Adaptive Evaluation, designed to learn at various levels of complexity while supporting the transformation needed to foster sustainable change. An Adaptive Evaluation uses three main approaches to work with complex questions—systems diagnosis, theorybased assessment of change processes, and iterative designs. An Adaptive Evaluation typically builds hypotheses from field-based interactions, emphasizes learning over testing, advocates open-mindedness with techniques, and appreciates the value of dialogue and participation in navigating complex processes. It can use RCT or similar techniques to analyse specific processes within a system or a development cycle, but these are embedded in a broader approach to assessment and interpretation. It is designed to be flexible and adjust to shifting contexts. Finally, an Adaptive Evaluation can be applied at any stage in a complex intervention's lifecycle, from the interpretation of the system and change processes to rapid experimentation, prototyping, and testing of select interventions, and then adaptation to different settings for impact at scale. This paper provides the theoretical basis for an Adaptive Evaluation—the main approaches, core ideology, process, and applications.

Technical assistance: a practical account of the challenges in design and implementation - Nastase, Alexandra; Rajan, Alok; French, Ben; Bhattacharya, Debarshi (Gates Open Research, 2021)
Technical assistance is provided to country governments as part of international development programmes to support policymaking or strengthen state capability. This article presents the conceptual evolution of ‘technical assistance’ linked to capacity development, starting with programmes aiming exclusively to enhance individual capacity in the 1950s to 1970s and progressing to complex systems approaches in the past ten years. It also presents some of the frequent challenges in designing and implementing technical assistance, drawing from the existing literature and the authors’ experience in international development. The article summarises the latest thinking about delivering more effective development, including the adaptive management practices and the initiatives to strengthen evidence about what works. Finally, we complement this article with a follow-up open letter reflecting on the current policy options and opportunities for change.

The high cost of accurate knowledge - Sutcliffe, Kathleen M.; Weber, Klaus (Harvard Business Review, 2003)
Many business thinkers believe it's the role of senior managers to scan the external environment to monitor contingencies and constraints, and to use that precise knowledge to modify the company's strategy and design. As these thinkers see it, managers need accurate and abundant information to carry out that role. According to that logic, it makes sense to invest heavily in systems for collecting and organizing competitive information. Another school of pundits contends that, since today's complex information often isn't precise anyway, it's not worth going overboard with such investments. In other words, it's not the accuracy and abundance of information that should matter most to top executives–rather, it's how that information is interpreted. After all, the role of senior managers isn't just to make decisions; it's to set direction and motivate others in the face of ambiguities and conflicting demands. Top executives must interpret information and communicate those interpretations–they must manage meaning more than they must manage information. So which of these competing views is the right one? Research conducted by academics Sutcliffe and Weber found that how accurate senior executives are about their competitive environments is indeed less important for strategy and corresponding organizational changes than the way in which they interpret information about their environments. Investments in shaping those interpretations, therefore, may create a more durable competitive advantage than investments in obtaining and organizing more information. And what kinds of interpretations are most closely linked with high performance? Their research suggests that high performers respond positively to opportunities, yet they aren't overconfident in their abilities to take advantage of those opportunities.
Keywords: Administrative Personnel; Data Collection; Decision Making; Organizational; Economic Competition; Information Management; Investments; Marketing; Organizational Innovation; United States

Fostering Learning in Large Programmes and Portfolios: Emerging Lessons from Climate Change and Sustainable Development - Harvey, Blane; Pasanen, Tiina; Pollard, Alison; Raybould, Julia (Sustainability, 2017)
In ﬁelds like climate and development, where the challenges being addressed can be described as “wicked”, learning is key to successful programming. Useful practical and theoretical work is being undertaken to better understand the role of reﬂexive learning in bringing together different knowledge to address complex problems like climate change. Through a review of practical cases and learning theories commonly used in the areas of resilience, climate change adaptation and environmental management, this article: (i) reviews the theories that have shaped approaches to reﬂexive learning in large, highly-distributed climate change and resilience-building programmes for development; and (ii) conducts a comparative learning review of key challenges and lessons emerging from early efforts to promote and integrate reﬂexive learning processes in programmes of this nature. Using a case study approach, the authors focus on early efforts made in four large, inter-related (or nested) programmes to establish, integrate and sustain learning processes and systems. Eight themes emerged from the review and are considered from the perspective of learning programmes as emergent communities of practice. By investigating how these themes play out in the nested programming, the paper contributes to the limited existing body of evidence on learning in large climate change programmes and identiﬁes areas where future efforts might focus.

What have we learned about learning? Unpacking the relationship between knowledge and organisational change in development agencies - Yanguas, Pablo (German Development Institute / Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Development cooperation has spent decades wrangling over the merits, evidence, and implications of what we may term “the learning hypothesis”: the idea that increased knowledge by development organisations must logically lead to increased effectiveness in the performance of their development activities. Organisations of all stripes have built research and monitoring and evaluation (M&E) departments, adopted a multitude of knowledge management systems and tools, and tinkered with different ways to structure their organograms to stimulate knowledge sharing and learning. The topic of organisational learning is particularly significant as the global development community grapples with increasingly complex problems and the aspiration of evidence-based policymaking. This paper presents an analytical framework for interrogating “the learning hypothesis”, breaking it down into causal steps: knowledge causes learning, learning causes organisational change, change causes effectiveness. The framework focuses on the first two sub-hypotheses, mapping out the conceptual space around them by outlining potential relationships between different types of knowledge – tacit and explicit, internal and external – and between different types of learning – operational and strategic. This map provides a foundation for three key research questions: What impact has the rising knowledge agenda had on development organisations? Which factors appear to enable or inhibit organisational learning? What is the relationship between operational and strategic learning and organisational change? A review of available evaluations and studies, including two cases from former UK Department for International Development (DFID) and the World Bank, reveals that there is insufficient evidence to support the causal claim that knowledge leads to learning and thereby to organisational change in development agencies. Sources point to tacit learning prevailing while explicit knowledge management systems flounder, and external advocacy agendas appear more compelling than internal research and evaluation products. It is not entirely clear how, or indeed, whether operational and strategic learning intersect, with delivery-level lessons hardly aggregating into structural or policy shifts. Organisational change – even that aimed at enhancing learning – is rarely based on lessons learned from practice. More research is necessary to fully unpack the learning hypothesis, but what limited evidence is available disproves rather than confirms its central claim. This has significant implications for the future of learning in development agencies as advocated by thought leaders, researchers, and reformers. In particular, the latter should consider an evidence-based reassessment of the function and value-for-money of research and M&E in development practice, and a more critical examination of the politics of external advocacy efforts around innovative aid approaches like thinking and working politically, adaptive management, or results-based management.
Version Number: 1.0

Planning & Navigating Social Change - Tools for Pacific voyagers - Orr, Douglas Epeli; Cavatore, Maria; Aston, Tom (Oxfam, 2019)
Those working to advance social change in the Pacific must understand, work with and respond to the complex and changing relationships and dynamics of power that exist within such networks, and situate their work in the context of decolonisation and self-determination. But the approaches typically used by NGOs to plan our projects and programs have failed to give due attention to these dynamics. The result is that our projects fall short of achieving their promise, despite being technically sound and logical. In this guide, we aim to provide a process and tools that prioritise and draw out the rich, often implicit, knowledge that Pacific Islanders have about our contexts to plan and manage social change initiatives in a manner that values and responds to this ocean of relationships. Drawing from these relationship-based and voyaging traditions, we emphasise the need to: • frame change in terms of change in people; e.g. change in the situation of groups of people and change in terms of the actions of people; • identify a course towards a particular ‘change destination’; • identify the signs to read that will help you determine where you are on that course; • be constantly attentive to the context as you make the journey, and • be ready to adjust your course in response to changes in your context. To support this way of working, we have selected a number of tools from approaches that we believe fit. In particular, we have drawn from the following approaches: • Thinking and Working Politically and other ‘politically aware’ approaches that recognise that the success of a development initiative will be determined by the interplay of relationships of power within a particular context, not just by having the right technical solution; • Outcome mapping because of its focus on people and relationships, and on identifying and supporting needed changes in the behaviour of specific actors in relation to others. This is key, because it’s individuals who deliver services, individuals who decide whether to allocate budget and resources to address a problem, and individuals who make the choice to believe whether a service is relevant to solving their issues; • Adaptive management because of its recognition that development initiatives take place within complex and changing systems and need to adjust to these and that this requires ongoing learning and adaptation.

A Guide to Digital Feedback Loops. An approach to strengthening program outcomes through data for decision making - Whittle, Dennis; Campbell, Megan (USAID, 2019)
Feedback is information about what happens as a result of what you do. Using that information to adapt what you do or how you do it creates what is called a feedback loop. A digital feedback loop uses digital technology at some stage of the feedback loop. Digital feedback loops help USAID missions improve the effectiveness and efficiency of their activities and can support partner countries on their journey to self-reliance through increased information sharing and improved government and civil society capacity. USAID missions and their partners have used digital feedback loops to improve HIV treatment targeting in Zimbabwe, engage three million young people in Nigeria in policy, and reduce field reporting times from one month to one day. Digital feedback loops provide access to information faster and more cheaply than ever before. As part of an adaptive management approach, digital feedback loops increase our ability to act on opportunities and respond to challenges. That in turn can improve outcomes and reduce the risk of waste and failure. This guide outlines the case for integrating digital feedback loops into your work, and provides tools, resources and guiding questions to support you as you get started. The guide includes examples of how USAID missions are using digital feedback loops to improve their programs in various sectors and provides worksheets to help you apply digital feedback loops to your own context.

Local Systems Position Paper - USAID (USAID, 2024)
The Local Systems Position Paper describes the key approaches USAID will use to translate systems thinking into systems practice. It focuses on ways USAID can better understand and engage local systems to support them in producing more sustainable results. Systems thinking is a mindset and set of tools that we use to understand how systems behave and produce certain results or outcomes. Systems practice is the application of systems thinking to better understand challenges and strengthen the capacity of local systems to unlock locally led, sustained progress. The shift from systems thinking to systems practice is driven by a desire to integrate systems practice throughout the Program Cycle and increase our capacity to actively and adaptively manage programming in ways that recognize complexity and help make our programs more effective and sustainable. These approaches will be utilized alongside and within the context of USAID’s policies and guidance, including technical guidance for specific sectors, as well as evidence and lessons learned from partners around the world. Systems thinking is a long-standing discipline that can serve as a powerful tool for understanding and working with local systems. It has been a consistent component of USAID’s decades-long commitment to locally led development and humanitarian assistance. USAID uses systems thinking to better understand the complex and interrelated challenges we confront – from climate change to migration to governance – and the perspectives of diverse stakeholders on these issues. When we understand challenges as complex systems – where outcomes emerge from the interactions and relationships between actors and elements in that system – we can leverage and help strengthen the local capacities and relationships that will ultimately drive sustainable progress. Recognizing this, in 2014, USAID released the Local Systems Framework, outlining ten principles to help USAID staff, partners, and local stakeholders place local systems at the center of all of our efforts to promote sustainability. Since then, development and humanitarian actors have embraced systems thinking as a concept and reiterated its importance in other policies, strategies, and tools, across sectors and regions. When USAID released its Localization Vision and Approach in 2022, it included local systems practice as a core component of adapting policies and program practices. Building on the success of the Local Systems Framework, this position paper reiterates USAID’s commitment to systems practice and presents six approaches that will help USAID strengthen and further embed systems practice in all of our work

Principles for managing in complexity - Proud, Emma (LearnAdapt, 2020)
Written by Toby Lowe and Shaheen Warren (Centre for Public Impact) and Sam Sharp (Overseas Development Institute), with input from Jamie…

Donor perceptions and processes: Risks to success of adaptive programming? - Browse - Knowledge Platform Security & Rule of Law - Donovan, Elbereth (Knowledge Platform - Security & Rule of Law, 2017)
Keywords: IMPORTANT

How can we be more adaptive? AdaptScan identifies critical areas for improvement - Mercy Corps (Mercy Corps & IRC, 2017)
Keywords: IMPORTANT

Adaptive Programming and Business Environment Reform – Lessons for DFID Zimbabwe - Donovan, Elbereth; Manuel, Clare (DFID, 2017)
Keywords: IMPORTANT

From analysis to action: operationalising learning and adaptation in Savings at the Frontier - Salehi, Yusef (2016)
Keywords: IMPORTANT

Learning, monitoring and evaluating: achieving and measuring change in adaptive programmes - Callaghan, Sarah; Plank, Georgia (DFID-LASER Programme, 2017)

Adaptive programming - Vowles, Pete (DFID Bloggers, 2013)
Staff blogs from the UK Department for International Development. Get real-life perspectives from those on the ground to fight poverty and join in the debate.

Course: Introduction to Collaborating, Learning and Adapting (CLA) in the Program Cycle - USAID LEARN (USAID Learning Lab, 2018)

Re-Perceiving Results: Aid Programs and Change in Fragile Societies - van Veen, Erwin; Rijper, Alies (Knowledge Platform Security & Rule of Law, 2017)
Aid programmes need to be able to adapt their objectives and operations to changes in their political environment, since development processes are subject to political contestation. Change takes time and is often a matter of seizing the opportunity.
Keywords: IMPORTANT

Politics matters, so what? Time for bigger bets (and more learning) on adaptive programming - Alan (www.globalintegrity.org, 2016)
By Alan Hudson, Executive Director, Global Integrity, July 26, 2016 Politics matters. Context too. And blueprints have limited value. Our strategy is based on these insights, so we’re totally on board. A World Development Report (WDR) that puts power and politics...

Adapting Aid: Lessons from six case studies - Algoso, Dave; Beloe, Jon; Hemberger, Alison; Hill, Philippa; Proud, Emma (MercyCorps & IRC, 2016)
Keywords: IMPORTANT

SAVI Approach Paper 15: Introduction to PERL: the SAVI Successor Programme - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

Nigeria Public Sector Accountability and Governance Programme - Business Case - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

Building capability by delivering results: Putting Problem-Driven Iterative Adaptation (PDIA) principles into practice - Andrews, Matt; Pritchett, Lant; Samji, Salimah; Woolcock, Michael (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Working between systems and complexity - a practitioners guide - Allen, Will (learningforsustainability.net, 2025)
How practitioners navigate between systems and complexity thinking. Exploring structure and emergence in real-world collaboration and adaptive work.

DFID’s approach to delivering impact - ICAI (Independent Commission for Aid Impact (ICAI), 2015)
UK aid, at its best, makes a real and positive difference to the lives and livelihoods of poor people around the world. Ensuring the best possible performance across a large and multifaceted aid programme is, however, a complex management challenge. This report reviews ICAI’s previous 44 reports and looks at how well DFID ensures positive, long-term, transformative impact across its work.

A New Policy Narrative for Pastoralism? Pastoralists as Reliability Professionals and Pastoralist Systems as Infrastructure - Roe, Emery (ESRC STEPS Centre, 2020)
This paper proposes that pastoralist systems are better treated, in aggregate, as a global critical infrastructure. The policy and management implications that follow are significant and differ importantly from current pastoralist policies and recommendations. A multi-typology framework is presented, identifying the conditions under which pastoralists can be considered real-time reliability professionals in systems with mandates preventing or otherwise avoiding key events from happening. The framework leads to a different policy-relevant counternarrative to pastoralism as understood today. Some features of the counternarrative are already known or have been researched. The paper’s aim is to provoke further work (including case research and interactions with decisionmakers) on how robust the counternarrative is as a policy narrative for recasting today’s pastoralist policy and management interventions.
Accepted: 2020-01-14T10:22:59Z

Announcement of CLA Learning Network Launch - Lab, Learning (USAID Learning Lab, 2016)
USAID’s Bureau for Policy, Planning and Learning (PPL), together with the Bureau for Economic Growth, Education, and Environment’s localworks program, is pleased to announce the launch of a Learning Network focused on building the evidence base for Collaborating, Learning and Adapting (CLA).

SAVI Approach Paper 5: Defining and Measuring Results - SAVI (DFID, 2015)
SAVI aims to facilitate replicable and sustainable processes of citizen engagement in governance. The programme in each state is locally defined, flexible and adaptive, and results are not predictable in advance. Standardised monitoring tools are not applicable, and consequently we have evolved our tools and frameworks during the programme through processes of learning by doing....

Essentials of Utilization-Focused Evaluation - Patton, Michael Quinn (SAGE Publications, 2011)
Based on Michael Quinn Patton's best-selling Utilization-Focused Evaluation, this briefer book provides an overall framework and essential checklist steps for designing and conducting evaluations that actually get used. The new material and innovative graphics present the utilization-focused evaluation process as a complex adaptive system, incorporating current understandings about systems thinking and complexity concepts. The book integrates theory and practice, is based on both research and professional experience, and offers new case examples and cartoons with Patton's signature humor.
Google-Books-ID: BaMgAQAAQBAJ
Keywords: Reference / Research; Research

Lessons for Effective resilience programs: a case study of the RAIN program in Ethiopia - Kleiman, Shanti (Mercy Corps, 2013)
The RAIN program experience affirms the importance of multi-year and flexible funding as key program design features if progress in resilience building is to be supported in areas with high levels of structural and temporal vulnerability. These features enable management to respond effectively to changing circumstances in order to better meet the needs of communities and to create the necessary conditions for relief-to-development strategies to take hold. Finally, this study found that deliberate and effective coordination between donor agencies can ensure that development gains achieved during one program period are directly leveraged by subsequent programs, thereby increasing the effectiveness of resilience programs.

The Rapid Evaluation, Action, and Learning (REAL) Approach: A toolkit to measure and refine changes and interventions in health campaigns - PATH (PATH, 2019)
Evaluative Tools for Improving Campaign Effectiveness Public health campaigns aim to control disease or deliver essential health services and products through time-limited and periodic channels. Many countries use campaigns to augment or replace routine service delivery, to target certain populations, or to accelerate progress towards coverage targets. The Root Cause Analysis and Rapid Evaluation, Action, and Learning toolkits present a systematic but flexible approach to identifying the root causes of campaign bottlenecks and then designing, testing, and refining solutions to optimize potential impact. These toolkits respond to a growing need for “fit-for-purpose” rapid-testing, adaptive learning approaches to evaluation and the need for a culture shift toward iterative adaptation and improvement that integrates measurement and evidence-informed decision-making into daily practice. The comprehensive package of toolkits, in addition to the individual Root Cause Analysis toolkit and Rapid Evaluation, Action, and Learning toolkit are available below.

USAID ADS 201 - Program Cycle Operational Policy (Update 1/23/2017) - USAID (USAID, 2017)
The Program Cycle is USAID’s operational model for planning, delivering, assessing, and adapting development programming in a given region or country to advance U.S. foreign policy. It encompasses guidance and procedures for: 1) Making strategic decisions at the regional or country level about programmatic areas of focus and associated resources; 2) Designing projects and supportive activities to implement strategic plans; and 3) Learning from performance monitoring, evaluations, and other relevant sources of information to make course corrections as needed and inform future programming.

Moving Targets, Widening Nets: monitoring incremental and adaptive change in an Empowerment and Accountability programme. The experience of the State Accountability and Voice Initiative in Nigeria - Derbyshire, Helen; Barr, Julian; Fraser, Steve; Mwamba, Wilf (DFID, 2016)
Keywords: IMPORTANT; Practice

Inclusive rigour for complexity - Chambers, Robert (Journal of Development Effectiveness, 2015)
Rigour can be reductionist or inclusive. To learn about and understand conditions of complexity, emergence, nonlinearity and unpredictability, the inclusive rigour of mixed methods has been a step in the right direction. From analysis of mixed methods and participatory approaches and methods, this article postulates canons for inclusive rigour for research and evaluation for complexity: eclectic methodological pluralism; improvisation and innovation; adaptive iteration; triangulation; plural perspectives; optimal ignorance and appropriate imprecision; and being open, alert and inquisitive. Inclusive rigour is inherent in participatory methods and approaches, visualisations, group-visual synergy, the democracy of the ground and participatory statistics. Transparent reflexivity, personal behaviour and attitudes, and good facilitation are fundamental. Fully inclusive rigour for complexity demands many personal, institutional and professional revolutions.
Keywords: Evaluation; Mixed methods; Participatory methodologies; Research; paradigm; rigour

Multi-project programmes functions, forms and implications for evaluation and learning - Buffardi, Anne; Hearn, Simon (Methods Lab, 2015)
Multi-project programmes can serve different purposes. For instance, they may coordinate multiple implementing entities; standardise management and technical support; compare intervention approaches across different contexts; enhance leverage through joint action; or foster sustainability by building relationships among organisations. • At the same time, multi-project programmes are costly, potentially duplicate other mechanisms that fulfil similar functions, and can dilute focus and create confusion. • To guide decisions on what coordination, evaluation and learning mechanisms are needed, it is helpful to articulate the intended purpose of using a programme model. Identifying the purpose(s) can help staff determine what types of knowledge sharing strategies may be most useful to the programme, and how project and programme theories of change can be sequenced

When theory meets reality: assumptions, feasibility and implications of a complexity-informed approach - Buffardi, Anne (Methods Lab, 2016)
Over the last half century, repeated calls for adaptive learning in development suggests two things: many practitioners are working in complex situations that may benefit from flexible approaches, and such approaches can be difficult to apply in practice. • Complexity thinking can offer useful recommendations on how to take advantage of distributed capacities, joint interpretation of problems and learning through experimentation in complex development programmes. • However, these recommendations rely on underlying assumptions about relationships, power and flexibility that may not hold true in practice, particularly for programmes operating in a risk averse, results-driven environment. • This paper poses guiding questions to assess the fit and feasibility of integrating complexity informed practices into development programmes.

Uncertainty and COVID-19: A turning point for Monitoring Evaluation, Research and Learning? - A discussion note for aid actors, policymakers and practitioners - Tyrrel, Lavinia; Roche, Chris; Jackson, Elisabeth (Abt Associates, 2020)
The COVID-19 pandemic has significantly shifted the context in which aid and development is being delivered. The global scale of the pandemic and the speed at which it is spreading mean that the ‘normal’ economic, ideological and organisational influences which shape (if not determine) aid delivery are in flux. This means that – for a relatively short-period – there is scope for aid actors to work collectively to embed more locally-led, politically-informed and adaptive forms of MERL in aid and development practice. These forms of Monitoring Evaluation Research and Learning (MERL) are not only well-suited to the current global pandemic. They also offer ways for aid program decision makers and practitioners to make sense of the complex and uncertain contexts in which much development work takes place. Applying locally-led, politically-informed and adaptive forms of MERL in the COVID-19 context and beyond requires a shift in mindset and approaches. Situations of complexity, in which it is difficult to predict the relationships between cause and effect, do not lend themselves to linear approaches and fixed indicators. Instead, they require ‘navigation by judgement’, ongoing learning and adaptation and greater privileging of local knowledge, and of the perspectives of those who are often excluded. Rather than being focused on upwards accountability, simple numbers and good news stories, the core function of MERL in this context is to support a better understanding – in real-time – of the changing operating context, to generate learning about the immediate impact of policy and program responses and their longer-term effects, and to inform decision making by front line staff. Whether the opportunities afforded by this ‘critical juncture’ are realised will depend on the degree to which those in the aid and development sector use this opportunity to promote a shift in the deep incentive structures within which development agencies are embedded. On the one hand, the pandemic underscores the limits of the linear understandings of change which underpin many orthodox approaches to planning, design and associated MERL. On the other hand, there is a vested interest in the status quo amongst many organisations, consultants, researchers and MERL practitioners. This is because approaches which promote locally-led development inevitably require those in power to relinquish control. While a range of factors make this shift difficult, there is more scope to change internal ways of working in development agencies than is commonly acknowledged. There is no time like the present to advocate for a ‘new normal’ for MERL.

Decision-Making and Data Use Landscaping [at DFID] - Powell, Josh; Orton-Vipond, Sarah; Bhatia, Vinisha; Kilroy, Annie (Development Gateway, 2018)
As DFID aims to harness the Data Revolution, ensuring that data1 drive decision-making, public accountability, and the achievement of the Sustainable Development Goals (SDGs), ensuring that systems, processes, and skills for data are aligned with these objectives is paramount. Across sector policy teams, country offices, and various analytical and technical cadres, different strengths and weaknesses, as well as needs and ambitions exist. To inform a strategic approach to data, as framed in its forthcoming Data Roadmap, DFID collaborated with Development Gateway to perform a Decision and Data Use Landscaping study. This report details lessons learned from approximately 60 interviews across 4 DFID country offices, all sector policy teams, senior managers, and various analytical and technical cadres and offices.

Adaptive programming in practice: shared lessons from the DFID-funded LASER and SAVI programmes - Derbyshire, Helen; Donovan, Elbereth (DFID-LASER Programme, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others).
Keywords: IMPORTANT; Practice

Impact evaluation for portfolio programmes on policy influence: Reflections on the Indonesian Poverty Reduction Support Facility - Mackenzie, Jessica; Hearn, Simon (Methods Lab, 2016)
• Donors are increasingly using portfolio-based programmes that embrace ‘good failure’ and adaptive, political programming. • However, measuring the impact of these programmes is challenging, especially for those working on policy influence and building country systems; not only do you need to measure the positive and negative impact of the overall portfolio, but also the different pathways tested. • Programmes, therefore, need a light-touch monitoring and evaluation system that allows it to remain flexible. • Good practice examples of portfolio-based programmes present six strategies to evaluate impact: 1. Develop appropriate logic models 2. Collect observational data throughout implementation 3. Develop stories of change or case studies 4. Understand causal relationships without a counterfactual 5. Purposefully select which activities to study 6. Be explicit about how impact will be valued across the portfolio. • These strategies are only useful if monitoring and evaluation is placed at the centre of programme decision-making.

The Limits of Institutional Reform in Development: Changing Rules for Realistic Solutions - Andrews, Matt (Cambridge University Press, 2013)
Institutional reforms are common across the globe. Think of efforts to build new governments in Afghanistan and Iraq; or decades worth of interventions intended to improve fiscal management, reduce corruption or introduce efficient public sector service delivery in African countries.These reforms often have limited results, however. They lead to new laws that are not properly implemented, and new organizations that have poor capacities and fail to function as needed. In this book, Matt Andrews explains why reform results are frequently limited and suggests ways to overcome these limits. In the first half of the book, Andrews argues that reforms fail to make governments better when they are introduced as signals to gain short-term support–from donors and others. Reforms as signals introduce unrealistic best practices that do not fit developing country contexts and are not considered relevant by implementing agents. The result is a set of new forms that do not function properly. Andrews uses examples to prove this point, ranging from efforts to introduce fiscal rules in Argentina to reforms aimed at international accounting standard adoption in many African countries, and anti corruption interventions in Malawi and Uganda. In the second half of the book, Andrews notes that there are instances where reforms are not being introduced as signals, and are having more of an impact on government effectiveness. Examples include local government reforms in Rwanda, anti corruption initiatives in Indonesia, and a variety of initiatives ranging from results based management to civil service modernization and internal control regime adoption in governments like Kenya, Kosovo and Afghanistan. Andrews uses these examples to discuss ways in which reforms can actually provide realistic solutions to governance challenges in developing countries. Lessons from these experiences suggest that reform limits can be overcome by focusing interventions on problem solving, and promoting incremental and localized processes to find solutions, involving multiple agents who can authorize and implement reforms.

Peer reviews - Guidance for facilitators and participants - Wadley, Ian (Centre for Humanitarian Dialogue, 2021)
Essential points for practitioners and donors • Mediation offers a cost-effective and proven method for resolving armed conflict. Between 1985 and 2015, 75 per cent of armed conflicts in the world were resolved through agreement rather than by force. In most cases these processes will have involved third party facilitation or support. • Professional mediators understand the high stakes involved in their work to prevent, mitigate and resolve armed conflict. In addition, they and their financial supporters are increasingly required to demonstrate ‘value-for-money’ to ensure continued funding. • However, traditional monitoring and evaluation (M&E) methods are not well suited to this task, typically imposing artificially linear project models on a dynamic conflict situation, as well as compliance reporting that moves attention away from real value. • Traditional M&E methods tend to focus on documenting the past and generating vast amounts of data, rather than enabling timely adaptation of the project in the present. • Traditional M&E approaches rely heavily on external evaluation consultants. Even in the best of cases this may interfere with the mediation process and impose a heavy time burden on the project team, leading to low acceptance of traditional M&E approaches by mediation practitioners. • In contrast, an ideal M&E approach for mediation should deliver useful insights in even the most dynamic and sensitive mediation environments, impose a light reporting burden, and be readily accepted by mediation teams. It should protect discretion and trust, enable rapid adaptation, and also provide some assurance that donor funds are being well spent.

The Politics of Evidence and Results in International Development: Playing the Game to Change the Rules? - Eyben, Rosalind; Guijt, Irene; Roche, Chris; Shutt, Cathy (Practical Action Publishing, 2015)
Understanding and demonstrating the effectiveness of efforts to improve the lives of those living in poverty is an essential part of international development practice. But who decides what counts as good or credible evidence? Can the drive to measure results do justice to and promote transformational change change that challenges the power relations that produce and reproduce inequality, injustice and the non-fulfillment of human rights? The Politics of Evidence in International Development provides a critical examination of the results agenda, with practical strategies for rendering it more helpful in supporting transformative development. The book deconstructs the origins and concepts of the results and evidence agendas employed in international development. It describes with concrete examples the current effects and consequences of the agenda, and goes on to outline a range of strategies used by individuals and organizations to resist, adapt or comply with the useful and problematic demands for results-oriented measurement and evidence of value for money."

Practicing what we preach — our experience rethinking M&E in complex settings - Bina, Andrea; Vester, Søren (UNDP Strategic Innovation, 2023)
The UNDP has been exploring new approaches to M&E to better understand and address complex systems challenges. Traditional linear project-based planning and evaluation methods are insufficient for dealing with the unpredictable nature of such systems. The UNDP’s new Strategic Plan calls for a shift in M&E practices to align with the complexity of today’s global challenges. Key points from the blog post include: Learning and Adapting: There’s a need for continuous learning and adaptation in M&E practices to effectively address complex problems like transitioning to a circular economy. Longer Time Horizons: Substantive change takes time, and it’s often unclear what the results will look like, making it difficult to track progress. Aggregate Impact: Evaluating interconnected interventions as a portfolio is crucial because they cannot be assessed in isolation. Contribution vs. Attribution: Focusing on the contribution to broader change processes is more important than attributing specific outcomes to individual actions. The UNDP has initiated the M&E Sandbox to experiment with and learn from innovative M&E practices. This collaborative space has attracted participants from over 180 organizations, highlighting a shared interest in evolving M&E to better understand change in contexts of uncertainty. A partnership with the Bill and Melinda Gates Foundation has also been formed to focus on M&E in food systems. The blog post emphasizes the importance of embracing uncertainty, experimenting, and collaborating to contribute to positive change in complex settings1.

Where have we got to on adaptive learning, thinking and working politically, doing development differently etc? Getting beyond the People’s Front of Judea - Algoso, Dave; Hudson, Alan (From Poverty to Power, 2016)
Dave Algoso and Alan Hudson at Global Integrity compare and contrast 9 different initiatives that are all heading in roughly the right direction in aid reform
Keywords: IMPORTANT

Valuing peace: delivering and demonstrating mediation results - Dilemmas & options for mediators - Wadley, Ian (Centre for Humanitarian Dialogue, 2017)
Essential points for practitioners and donors • Mediation offers a cost-effective and proven method for resolving armed conflict. Between 1985 and 2015, 75 per cent of armed conflicts in the world were resolved through agreement rather than by force. In most cases these processes will have involved third party facilitation or support. • Professional mediators understand the high stakes involved in their work to prevent, mitigate and resolve armed conflict. In addition, they and their financial supporters are increasingly required to demonstrate ‘value-for-money’ to ensure continued funding. • However, traditional monitoring and evaluation (M&E) methods are not well suited to this task, typically imposing artificially linear project models on a dynamic conflict situation, as well as compliance reporting that moves attention away from real value. • Traditional M&E methods tend to focus on documenting the past and generating vast amounts of data, rather than enabling timely adaptation of the project in the present. • Traditional M&E approaches rely heavily on external evaluation consultants. Even in the best of cases this may interfere with the mediation process and impose a heavy time burden on the project team, leading to low acceptance of traditional M&E approaches by mediation practitioners. • In contrast, an ideal M&E approach for mediation should deliver useful insights in even the most dynamic and sensitive mediation environments, impose a light reporting burden, and be readily accepted by mediation teams. It should protect discretion and trust, enable rapid adaptation, and also provide some assurance that donor funds are being well spent.

Diseño transformacional de proyectos - Kehrer, Daniel (GIZ, 2020)
There are many definitions of the term ‘transformation’ or ‘transformational change’. The first section of the report develops a basic understanding of transformations or transitions (used synonymously) viewed from various perspectives. In this, transformations are defined as processes that use disruptive innovations to change systems into fundamentally new systems that subsequently form the new mainstream. Section two describes existing approaches to environmental and climate finance in international cooperation and discusses them in light of the proposed definition. All of the approaches have the potential to be further refined and in that process often to increase the precision of what is understood by each type of transformation. The definitions already state which criteria and indicators are referred to and how relevant they are. There is wide diversity in the type of criteria and indicators used by the various organisations, and how they are classified, but certain common features can be identified and with the aid of the literature on transformations they can be combined to form a comprehensive framework. With this in mind, the derivation of quality criteria for transformative interventions is explained in section 3.1. Transformational change at one and the same time calls for big decisions and innumerable projects in a particular field of transformation; the projects cannot be planned on the drawing board but still should be coordinated with each other. Section 3.2 offers guidance on this. Section 3.3 argues in favour of focusing more closely on the ‘process promise’ and employing a more iterative and more adaptable commissioning procedure. Finally, section 3.4 introduces two types of indicators under the various criteria: design indicators, which measure the quality of interventions that are aimed at influencing transformations (process orientation), and outcome indicators, which measure the process and/or progress of a transformation itself.

Aid on the Edge of Chaos: Rethinking International Cooperation in a Complex World - Ramalingam, Ben (Oxford University Press, 2014)
It is widely recognised that the foreign aid system - of which every country in the world is a part - is in need of drastic overhaul. There are conflicting opinions as to what should be done. Some call for dramatic increases to achieve longstanding promises. Others bang the drum for cutting it altogether, and suggest putting the fate of poor and vulnerable people in the hands of markets or business. A few argue that what is needed is creative, innovative transformation. The arguments in Aid on the Edge of Chaos are firmly in the third of these categories. In this ground-breaking book, Ben Ramalingam shows that the linear, mechanistic models and assumptions that foreign aid is built on are more at home in early twentieth century industry than in the dynamic, complex world we face today. The reality is that economies and societies are less like machines and more like ecosystems. Aid on the Edge of Chaos explores how thinkers and practitioners in economics, business, and public policy have started to embrace new, ecologically literate approaches to thinking and acting, informed by the ideas of complex adaptive systems research. It showcases insights, experiences, and dramatic results of a growing network of practitioners, researchers, and policy makers who are applying a complexity-informed approach to aid challenges. From transforming approaches to child malnutrition, to rethinking process of macroeconomic growth, from rural Vietnam to urban Columbia, Aid on the Edge of Chaos shows how embracing the ideas of complex systems thinking can help make foreign aid more relevant, more appropriate, more innovative, and more catalytic. It argues that taking on these ideas will be a vital part of the transformation of aid, from a post-WW2 mechanism of resource transfer, to a truly innovative and dynamic form of global cooperation fit for the twenty-first century.

Social Accountability 3.0: Engaging Citizens to Increase Systemic Responsiveness. Background Paper - Guerzovich, Florencia; Aston, Tom (Grupo Politeia, ESAG, UDESC and act4delivery, 2024)
Social accountability has become increasingly important to development programming since the 2004 World Development Report spearheaded its first generation of programming. In 2016, Thomas Carothers synthesized global experts’ perspectives on what became known as the second generation. With an evolving global context, new research and evaluations and tacit knowledge on how those assumptions played out in practice, the time is ripe for asking what the evidence since 2004 can tell us about what the social accountability’s next generation might look like? This meta-analysis takes stock of that knowledge through a systems lens and presents a possible “social accountability 3.0.” It draws on a database of 157 cases of initiatives implemented by different civil society organizations around the world and the lived experience of practitioners. Scholarly debates present practitioners’ options in binary terms, contrasting 1.0 minimalist and 2.0 maximalist options. The review finds that this binary is inaccurate and misleading; it masks practitioners’ diverse interpretations of 2.0 and range of feasibility considerations. Instead, work in the last decade looks more like a mosaic. By opening the analysis to the broader range of evidence, and reflecting more critically on scholars’ assumptions, a more adaptable middle path for social accountability 3.0 emerges. Its key outcomes include contributing to systemic responsiveness and an operational mechanism to rework the social contract.

Transformative project design - Kehrer, Daniel (GIZ, 2020)
There are many definitions of the term ‘transformation’ or ‘transformational change’. The first section of the report develops a basic understanding of transformations or transitions (used synonymously) viewed from various perspectives. In this, transformations are defined as processes that use disruptive innovations to change systems into fundamentally new systems that subsequently form the new mainstream. Section two describes existing approaches to environmental and climate finance in international cooperation and discusses them in light of the proposed definition. All of the approaches have the potential to be further refined and in that process often to increase the precision of what is understood by each type of transformation. The definitions already state which criteria and indicators are referred to and how relevant they are. There is wide diversity in the type of criteria and indicators used by the various organisations, and how they are classified, but certain common features can be identified and with the aid of the literature on transformations they can be combined to form a comprehensive framework. With this in mind, the derivation of quality criteria for transformative interventions is explained in section 3.1. Transformational change at one and the same time calls for big decisions and innumerable projects in a particular field of transformation; the projects cannot be planned on the drawing board but still should be coordinated with each other. Section 3.2 offers guidance on this. Section 3.3 argues in favour of focusing more closely on the ‘process promise’ and employing a more iterative and more adaptable commissioning procedure. Finally, section 3.4 introduces two types of indicators under the various criteria: design indicators, which measure the quality of interventions that are aimed at influencing transformations (process orientation), and outcome indicators, which measure the process and/or progress of a transformation itself.

Monitoring, Evaluation and Learning for Systems Change - McDonald, Lizzy; Simpson, Kate; Schramm, Carolin (Wasafiri, 2025)
Today’s critical challenges are complex and require system level change. Issues like ending poverty, reversing biodiversity collapse, creating more equitable and sustainable food systems, or ending health inequalities, will not respond to neat siloed technical interventions. These are not problems we can tackle head on. Rather, we need to change the conditions (systems) that create these problems. Consequently, many of the most ambitious philanthropic foundations are adopting ‘systems change’ approaches to their work. There is a critical need to better understand the impact of systems change interventions. This is for two reasons: 1) without being able to understand our impact we can’t learn about the efficacy of efforts and focus on doing more helpful action and less unhelpful action, and 2) without effective monitoring and evaluation it is hard to galvanise resources, whether as money, time, or enthusiasm. Traditional monitoring, evaluation and learning (MEL) approaches and practices struggle to respond to complexity. Many of today’s MEL approaches have been developed to serve funders keen to ‘prove’ the efficacy of their work and hold grantees accountable. This paradigm has produced approaches like ‘logical frameworks’ that seek to create a linear logic between intervention, outputs, outcomes and impact. Such approaches often pay scant regard to the activity (intentional or otherwise) of other actors in any system, and don’t adapt well to the characteristics of complex problems such as emergence, uncertainty, and interdependency. There is a fast-developing body of practice on MEL for systems change. A growing number of practitioners are experimenting with complexity informed approaches to MEL, and UNDP is pioneering an open-source set of tools and ideas.ii Wasafiri is contributing to this innovation by developing a MEL approach that builds on our (open access) Systemcraft Framework. iii Emerging approaches for systems change MEL are underpinned by some key principles. There is growing consensus on the need to be pragmatic and flexible, not just because it is a new field for many that requires a degree of mindset and behaviour change and different ways of working. MEL approaches for system change primarily focus on improving and learning and on identifying ways to adapt and pivot. This contrasts with linear approaches to implementation and measurement. Learning questions guide and co-exist alongside indicators to support continual learning and adaptation. These shifts will require a shift in relationships between funders and implementers from measuring and accountability to greater flexibility and patience, close engagement and learning together. There is pressure to show impact in less time. Reduced time horizons, increasing impatience and integration of new sets of agendas in development programming present challenges in the context of systems change. In an increasingly resource constrained context and amid growing global uncertainty (e.g. current global politics, emergencies like COVID, economic instability, rapid technological advancement), it is unclear which direction donors will take, i.e. an even greater focus on value for money and impact, and/or willingness to explore innovative approaches and learning in uncertain territory. Wasafiri’s approach for systems MEL builds on Systemcraft. This is a diagnostic and design tool for systems change, that has been used globally across a broad range of systems and interventions. This paper summarises our approach to MEL for systems change. It aims to provide a short introductory overview and form a ‘conversation starter’ to initiate a practical dialogue on current practices, experiences, and learnings with MEL for systems change. It introduces some concepts and appropriate tools for measuring systems change and poses some key questions for further discussion. We aim to engage with funders and practitioners working on complex problems who are in the process of or planning to develop their approach to and practices for MEL, who are interested to learn, share and explore. We welcome your inputs, either in response to this document, via a call, or during online webinars that we will convene in 2025.

Integrated Governance: Achieving Governance Results and Contributing to Sector Outcomes - Frazer, Sarah; Granius, Mark; Brinkerhoff, Derick W.; McGregor, Lisa (RTI Press, 2022)
Achieving broad-based socio-economic development requires interventions that bridge disciplines, strategies, and stakeholders. Effective sustained progress requires more than simply an accumulation of sector projects, and poverty reduction, individual wellbeing, community development, and societal advancement do not fall neatly into sectoral categories. However, researchers and practitioners recognize key operational challenges to achieving effective integration that stem from the structures and processes associated with the current practice of international development. Integration calls for the intentional linking of intervention designs, implementation, and evaluation across sectors and disciplines to achieve mutually reinforcing outcomes. In this report, we summarize the results of a study we conducted to explore the challenges facing governance programs that integrate with sector interventions to achieve governance outcomes and contribute to sector outcomes. Through a review of policy documents and project reports from recent integrated governance programs and interviews with donor and practitioner staff, we found three integrated governance programming variants, an emphasis on citizen and government collaboration to improve service delivery, interventions that serve as the glue between sectors, and a balancing act for indicators to measure contribution to sectoral outcomes. Our analysis identified four key success factors: contextual readiness, the application of learning and adapting approaches, donor support, and recognition of the limitations of integrated governance. We then discuss recommendations and implications and for answering the challenge of integrating governance and sector programming to achieve development outcomes.

Global governance and local peace: accountability and performance in international peacebuilding - Campbell, Susanna (Cambridge University Press, 2018)
Local peacebuilding and global accountability – The country context–Burundi from 1999 to 2014 – Ingos in peacebuilding–globally unaccountable, locally adaptive – International organizations in peacebuilding–globally accountable, locally constrained – Bilateral development donors–accountable for global targets, not local change
OCLC: 1048387754

Politically smart approaches to donor investment climate programming. A Guidance Note - LASER (DFID-LASER Programme, 2016)
In order to help enhance the effectiveness of donors and development practitioners on the ground, LASER has produced a range of practical guidance and tools. These are primarily intended for the international development community engaged in designing and implementing investment climate programmes, though can also be used more widely by other stakeholders across sectors. General guidance and tools: Politically smart approaches to donor investment climate programming (and annexes) Revised February 2016 - sets out practical advice on how to adopt a politically smart (which requires being both ‘politically informed’ and ‘politically astute’) approach to programming. The annexes include a traffic light matrix for initial high level analysis; a problem diary template with examples; and an example of a flexible theory of change for adaptive, large scale programming
Keywords: Practice

The SAVI programme in Nigeria: Towards politically smart, locally led devlopment - Booth, David; Chambers, Victoria (ODI, 2014)
 More examples are needed of aid programming that works by being responsive to country realities: politically smart, problem-driven and locally led  DFID’s SAVI programme has revealed a hitherto untapped potential for change leading to better development results at state level in Nigeria  SAVI provides low-profile support to state-level organisations and partnerships, building their capacity to engage constructively with government  It avoid the pitfalls of a donor-driven approach by ‘taking the money off the table’  This illustrates the power of facilitated multi-stakeholder engagement and the disadvantages of seeing this in terms of ‘supply side’ and ‘demand side’ governance  The set-up of the DFID suite of state-level programmes, with separately managed sector support and ‘governance’ initiatives, has limited realisation of the potential  Key enabling conditions were that DFID provided space for an experience-based design process and permitted tangible results to be judged retrospectively, not pre-programmed

Understanding Political Economy Analysis and Thinking and Working Politically - Whaites, Alan; Piron, Laure-Hélène; Menocal, Alina Rocha; Teskey, Graham (FCDO and TWP CoP, 2023)
This guide is adapted from work by the UK Foreign, Commonwealth and Development Office (FCDO) with inputs from members of the Thinking and Working Politically Community of Practice (TWP CoP). It outlines how to understand and use a set of analytical tools that are collectively known as Political Economy Analysis (PEA). The guide aims to equip practitioners to act in an informed manner, given that development objectives are invariably politically complex, and entail engaging with counterparts’ political incentives and preferences. The guide summarises different types of tools – from very light-touch to more in-depth approaches – and provides advice on how development professionals can decide what is most appropriate in a given context, with illustrations based on the experiences of teams working on these issues. This guide will help development professionals and others to make use of PEA and to apply it to their own specific needs. The first part of the guide offers a general picture of the approach. The second part provides more specific guidance for those who are tasked with deploying a PEA. Contents –> Main audience What is PEA, its role and purpose (Section 2) –> General information for all readers The main elements of PEA (Section 3) Thinking and Working Politically (Section 4) –> Core information for teams planning and using PEA How to ensure quality (Section 5) –> Essential reading for those directly responsible for a PEA Important concepts and terminology (Annex) –> General information for all readers

A Framework for Embedding Learning in Systems Change - Bertermann, Kecia; Coffman, Julia (Center for Evaluation Innovation, 2024)
This five-step framework, developed and tested by a foundation, embeds learning in emergent systems change strategies. It prioritizes the testing of hypotheses and assumptions, uses learning questions, and calls for examining both confirming and disconfirming evidence. — A framework for embedding learning in systems change strategies and for testing strategic uncertainties. Learning and evaluation approaches that accompany systems change efforts need to fit with and support the emergent nature of this work. Systems change efforts call for examining, with evidence, the hypotheses and assumptions that undergird the work and regularly adapting in response to what is learned. They require staff to be highly engaged in testing their ideas by gathering evidence, interpreting it, and then acting on its implications. This brief presents a learning approach—referred to here as the Learning Framework—developed and tested by a foundation to support its systems change strategies. It is intended for other practitioners working on approaches for integrating learning with systems change efforts. Because a wealth of conceptual work exists about why learning is critical to systems change but practical advice about how to do it is much less available, we describe the approach we took and how the Framework’s core elements fit together in practice. The primary purpose of this approach is to interrogate our strategic uncertainties. This approach to learning is different from the dominant approach to learning and evaluation in philanthropy that primarily looks for evidence (often static metrics) that expected outcomes have been achieved (an approach that is more suitable for linear and predictable change strategies). This Learning Framework is driven by, and organized around, hypotheses and assumptions. This is especially important for systems change efforts where the path forward cannot be determined with complete certainty, but where robust evidence collection and regular sensemaking can increase our confidence in chosen directions and ultimately increase our chances of success.

Guidance: Rigor and Reproducibility in Grant Applications | grants.nih.gov - NIH (National Institutes of Health, 2018)

Seeing the Combined Effects of Aid Programmes - Burge, Richard; Nadelman, Rachel; McGee, Rosie; Fox, Jonathan; Anderson, Colin (Institute of Development Studies, 2022)
Multiple aid agencies often try to support change in the same places, at the same time, and with similar actors. Surprisingly, their interactions and combined effects are rarely explored. This Policy Briefing describes findings from research conducted on recent aid programmes that overlapped in Mozambique, Nigeria, and Pakistan, and from a webinar with UK Foreign, Commonwealth & Development Office (FCDO) advisors and practitioners. The research found three distinct categories of ‘interaction effects’: synergy, parallel play, and disconnect. We explore how using an ‘interaction effects’ lens in practice could inform aid agency strategies and programming.
Accepted: 2022-05-10T09:42:35Z

Rapid experiments with a purpose - Moses, Michael (BEAM Exchange, 2017)
New insights, opinions and perspectives on market systems development, from experts and practitioners.
Keywords: IMPORTANT

Black Box Thinking: The Surprising Truth About Success - Syed, Matthew (Hachette UK, 2015)
The Sunday Times No.1 Bestseller From the Bestselling Author of BounceWhat links the Mercedes Formula One team with Google?What links Team Sky and the aviation industry?What connects James Dyson and David Beckham?They are all Black Box Thinkers.Black Box Thinking is a new approach to high performance, a means of finding an edge in a complex and fast-changing world. It is not just about sport, but has powerful implications for business and politics, as well as for parents and students. In other words, all of us.Drawing on a dizzying array of case studies and real-world examples, together with cutting-edge research on marginal gains, creativity and grit, Matthew Syed tells the inside story of how success really happens - and how we cannot grow unless we are prepared to learn from our mistakes.
Google-Books-ID: f1eNBQAAQBAJ
Keywords: Psychology; Sports & Recreation / Sports Psychology; Strategic Planning

Using what we know: How to ensure tech projects meet the brief - Walker, Tom (Making All Voices Count, 2017)
Making tech effective - building on what we already know

A ‘real-time’ and anthropological response to the Ebola crisis - IDS (IDS, 2017)
Impact Summary The Ebola epidemic that began in the Guinea-Sierra Leone-Liberia border region in December 2013 spread fast through the villages, cities and trade routes of this highly-peopled,...

Barrio Mio and Katye: PCI’s neighbourhood approach in cities - Campbell, Leah (ALNAP/ODI, 2019)

Good Enough Governance Revisited - Grindle, Merilee S. (Development Policy Review, 2007)
The concept of good enough governance provides a platform for questioning the long menu of institutional changes and capacity-building initiatives currently deemed important (or essential) for development. Nevertheless, it falls short of being a tool to explore what, specifically, needs to be done in any real world context. Thus, as argued by the author in 2004, given the limited resources of money, time, knowledge, and human and organisational capacities, practitioners are correct in searching for the best ways to move towards better governance in a particular country context. This article suggests that the feasibility of particular interventions can be assessed by analysing the context for change and the implications of the content of the intervention being considered.

Is there a new Washington Consensus? An analysis of five World Development Reports - Evans, Alice (From Poverty to Power, 2017)
Is there a new Washington Consensus? Alice Evans analyses the last five World Development Reports and finds significant changes in orthodoxy, but also big gaps

Still watering white elephants? The blueprint versus process debate thirty years on - Booth, David (Perspectives on politics, production and public administration in Africa: essays in honour of Ole Therkildsen, 2015)
OCLC: 913447024

Impact assessment and the quest for the Holy Grail - Bymolt, Roger (KIT Royal Tropical Institute, 2015)

Planners versus Searchers in Foreign Aid - Easterly, William (Asian Development Review, 2006)
Only for the recipients of foreign aid is something akin to central planning seen as a way to achieve prosperity. The end of poverty is achieved with free markets and democracy—where decentralized “searchers” look for ways to meet individual needs—not Poverty Reduction Strategy Papers (PRSPs) to achieve Millennium Development Goals (MDGs). The PRSPs and MDGs create lots of bureaucracy but hold no one specific agency in foreign aid accountable for any one specific task. Planners in foreign aid use the old failed models of the past—the “Financing Gap”, the “poverty trap”, the government-to-government aid model; and the “expenditures = outcomes” mentality. Searchers in foreign aid would imitate the feedback and accountability of markets and democracy to provide goods and services to individuals until homegrown markets and democracy end poverty in the society as a whole. An example of the more promising “searchers” approach in foreign aid is 2006 Nobel Peace Laureate Mohammad Yunus and Grameen Bank.

AID Programming Guide - DFAT (Australian Government, 2019)

Balancing Inclusiveness, Rigour and Feasibility: Insights from Participatory Impact Evaluations in Ghana and Vietnam - van Hemelrijck, Adinda; Guijt, Irene (CDI, 2016)
This paper by Adinda Van Hemelrijck and Irene Guijt explores how impact evaluation can live up to standards broader than statistical rigour in ways that address challenges of complexity and enable stakeholders to engage meaningfully. A Participatory Impact Assessment and Learning Approach (PIALA) was piloted to assess and debate the impacts on rural poverty of two government programmes in Vietnam and Ghana funded by the International Fund for Agricultural Development (IFAD). We discuss the trade-offs between rigour, inclusiveness and feasibility encountered in these two pilots. Trade-offs occur in every impact evaluation aiming for more than reductionist rigour, but the pilots suggest that they can be reduced by building sufficient research and learning capacity.

PDIA Notes 2: Learning to Learn - Samji, Salimah (Building State Capability, 2016)
written by Peter Harrington After over two years of working with the government of Albania, and as we embark on a new project to work with the government of Sri Lanka, we at the Building State Capa…

Summarising portfolio change: results frameworks at organisational level - Simister, Nigel (Intrac, 2016)

Mission-Based Monitoring, Evaluation and Learning (MEL) Platforms Assessment Report - Arntson, Laura; Giannoni, Tonya; Peek, Nancy; Saarlas, Kristin (USAID, 2017)
In 2016, the Bureau of Policy, Planning and Learning (PPL) commissioned an internal stocktaking of USAID's mission-based MEL (Monitoring, Evaluation, and Learning) Platforms.

Fast Isn’t the Same as Forward - Brink (Brink's Cognitive Download, 2025)
What it takes to create smart velocity

RFI-521-17-000015 - Improving Governance in Haiti Program (IGHI) - USAID (USAID, 2017)

Enabling citizen-driven improvement of public services. Leveraging Technology to Strengthen Accountability in Nigerian Healthcare - ICT4SA (World Bank and Reboot, 2015)
Effective public service delivery begins with knowing whether the services offered are working as intended. We launched a system to enable citizen input on the delivery of public services.

Innovation for International Development: Navigating the Paths and Pitfalls - Ramalingam, Ben; Bound, Kirsten (NESTA, 2016)
Experiences, insights and practical advice from over 20 leading practitioners in innovation for international development, brought together in one collection.

Utilization-Focused Evaluation (U-FE) Checklist - Patton, Michael Quinn (The Evaluation Center, 2013)
Utilization-Focused Evaluation begins with the premise that evaluations should be judged by their utility and actual use; therefore, evaluators should facilitate the evaluation process and design any evaluation with careful consideration of how everything that is done, from beginning to end, will affect use. Use concerns how real people in the real world apply evaluation findings and experience and learn from the evaluation process. The checklist is based on Essentials of Utilization-Focused Evaluation (Patton, 2012, Sage Publications). All references in the checklist to exhibits and menus refer to this book. Step 1 Assess and build program and organizational readiness for utilization-focused evaluation. Step 2 Assess and enhance evaluator readiness and competence to undertake a utilizationfocused evaluation. Step 3 Identify, organize, and engage primary intended users. Step 4 Conduct situation analysis with primary intended users Step 5 Identify primary intended uses by establishing the evaluation’s priority purposes. Step 6 Consider and build in process uses if appropriate. Step 7 Focus priority evaluation questions. Step 8 Check that fundamental areas for evaluation inquiry are being adequately addressed. Step 9 Determine what intervention model or theory of change is being evaluated. Step 10 Negotiate appropriate methods to generate credible findings and support intended use by intended users. Step 11 Make sure intended users understand potential controversies about methods and their implications. Step 12 Simulate use of findings. Step 13 Gather data with ongoing attention to use. Step 14 Organize and present the data for use by primary intended users. Step 15 Prepare an evaluation report to facilitate use and disseminate significant findings to expand influence. Step 16 Follow up with primary intended users to facilitate and enhance use. Step 17 Metaevaluation of use: Be accountable, learn, and improve

Taking responsibility for complexity: how implementation can achieve results in the face of complex problems - Jones, Harry (ODI, 2011)
OCLC: 837825712

Learning From Failure 2020 - What CARE’s evaluations tell us about how to improve our work - CARE (CARE, 2020)
“Ever failed. No matter. Try again. Fail again. Fail better.” –Samuel Beckett Here’s my favorite part of that quote: the ultimate goal is not a lack of failure; it’s better failures. That’s good news for CARE, because we just published round two of our Learning From Failure initiative, and…I know this will surprise everyone…we haven’t stopped failures yet. We do have some hopeful signs that we’re failing better; or at least, that we’re improving on some concrete weaknesses we identified in the first round. It’s an interesting process to launch the second phase of learning from failure. The first round, we didn’t know what we were going to find. We spent as much time talking about how it was the first-ever report of its kind as we did about the actual failures. Our case study admitted, “It's still very early to see specific development impacts.” Round two isn’t quite the same. It’s not new anymore, so there’s less excitement at having invented something. We’re not discovering data and themes for the first time. In a lot of ways, the stakes are higher. Round two of learning from failure becomes an exercise in continuous performance improvement, rather than a journey of discovery. If we don’t see improvements, we don’t have the excuse that it’s too early to tell. It also takes a sustained commitment. Launching an exploratory exercise at a small scale is easy, especially when no one quite knows what the answers will be. Pulling together a few pieces of content over a few months is pretty straightforward. It takes some staying power—and real support from leadership—to keep up the work over time, especially in the middle of a pandemic. That’s even more true once we’ve seen one round of results and had a chance to understand the work that it takes to improve.

Behavioral Design: A New Approach to Development Policy - Datta, Saugato; Mullainathan, Sendhil (Review of Income and Wealth, 2014)

Thinking and working politically: What have we learned since 2013 - Teskey, Graham (TWP Community of Practice, 2021)
The Thinking and Working Politically (TWP) Community of Practice (CoP) was established at a small meeting tacked on at the end of a meeting of Governance Advisers working for the United Kingdom’s Department of International Development (DFID) on South and South-East Asian countries, held in Delhi in November 2013. Since then, a number of meetings have been held throughout the world, each addressing different issues; ‘TWP’ has entered the lexicon of mainstream development; the CoP has expanded to more than 300 people; a Washington DC chapter has been established; and the International CoP has been granted modest funding from DFID’s successor, the Foreign, Commonwealth and Development Office (FCDO) and from Australia’s Department of Foreign Affairs and Trade (DFAT). It is legitimate to ask, however, what has been achieved operationally: how have the ideas underpinning TWP affected operational practice? This short paper traces the evolution of the idea and practice of TWP from 2013 to late 2021, and identifies what we have learned. What has been successful, and what has not? I asked in 2017 whether TWP had become a second orthodoxy (Teskey, 2017). Did this represent hubris or was 2017 in some ways the apogee of what might rather grandly be called the TWP ‘movement’?

The Boda Boda Talk Talk Module - Internews (Internews & USAID, 2017)
Keywords: IMPORTANT

Thinking and Working Politically in Economic Development Programmes – Some Sprints and Stumbles from a DFID Programme in Kyrgyzstan - Koleros, Andrew; Rinnert, David (From Poverty to Power, 2019)
A DFID programme in Kyrgyzstan offers useful insights into how the Thinking and Working Politically approach can escape from its governance ghetto
Keywords: Case Study

Program Cycle - How-To Note: Strategy-Level Portfolio Review - USAID (USAID PPL, 2017)

Transforming our work: Getting ready for transformational projects - Kehrer, Daniel; Flossmann-Kraus, Ursula; Ronco Alarcon, Sabrina Valeria; Albers, Vivien; Aschmann, Gwendolin (GIZ, 2020)

One step back, two steps forward: CARE’s journey towards doing development differently - Aston, Tom (Care Insights, 2017)
The Doing Development Different (DDD) community emerged in August 2014 and advocates that (a) the barriers to development are as much political as tec...

SAVI Approach Paper 1: Core Values - SAVI (London, 2015)
Governance reform is about government and citizens working together in more responsive, inclusive and accountable ways for the benefit of citizens. More responsive, inclusive and accountable attitudes and behaviour on the part of government and non-government stakeholders are the critical factors which lead to meaningful reform processes, and replicate and sustain reforms beyond the lifetime...

SAVI Approach Paper 2: Programme Design - SAVI (DFID, 2015)
SAVI supports citizen engagement in governance through a facilitated partnership approach, in contrast to the usual approach of grants to civil society organisations (CSOs). The overall aim is to facilitate and support working relationships and processes of reform that are home-grown, self-sustaining and, after initial engagement, not dependent on external support. Our way of working...

SAVI Approach Paper 3: Theory of Change - SAVI (DFID, 2015)
SAVI’s theory of change is a simple, practical guide that staff and partners use to plan and to monitor change – as well as to reflect on and enhance their own effectiveness. It sets out broad stages of attitude and behaviour change over time to facilitate effective citizen engagement in governance processes, systems and structures....

SAVI Approach Paper 6: Engaging Civil Society - SAVI (DFID, 2015)
SAVI state teams provide support to CS groups to become more effective agents of citizens’ voice and public accountability, through a variety of mutually reinforcing interventions. These include: hands-on support to demonstration civil society Advocacy Partnerships (APs) facilitating working partnerships between civil society APs, SHoAs, and the media brokering working relationships between all of these...

SAVI Approach Paper 7: Promoting Gender Equality and Social Inclusion - SAVI (DFID, 2015)
We promote attention to gender equality and social inclusion in all of our engagement with CS groups, the media and SHoAs, and in all of the issues and processes they work on. In all the states we work in, we also support partners to focus on some issues and form some partnerships and networks which...

SAVI Approach Paper 8: Engaging the Media - SAVI (DFID, 2015)
The overall aim of SAVI engagement with the media is for media representation of citizens’ interests to become normal, and play its part in helping state governments to be more responsive, inclusive and accountable to their citizens. Media partners – individual media personnel and selected media houses – are supported to be more effective agents...

SAVI Approach Paper 9: Engaging State Houses of Assembly - SAVI (DFID, 2015)
The overall aim of SAVI engagement with SHoAs is to promote lasting reforms that are not dependent on external funding and which promote an increasingly more responsive and accountable relationship between Nigerian state governments and their citizens. SHoAs are supported to be more effective agents of citizen voice and public accountability, demanding better performance from...

SAVI Approach Paper 10: Engaging State Governments - SAVI (DFID, 2015)
SAVI as a programme does not directly work with state governments – but we work in close conjunction with sister programmes who are supporting state governments on governance and sector reforms. SAVI supports non-government and SHoA partners to play their part in promoting more responsive, inclusive and accountable state governance delivering better services for citizens....

USAID ADS 201 - Program Cycle Operational Policy (Update 10/29/2018) - USAID (USAID, 2018)

ADS 201 Additional Help- Whole-of-Project Evaluation - USAID (USAID, 2017)

‘We have the solutions to our own problems’: supporting civil society in Nigeria - Overseas Development Institute (ODI, 2014)
Development assistance programmes that start from careful analysis of what works and what does not in country contexts are still remarkably rare. One reason for this is the lack of well documented examples of ‘politically’ smart aid programming. To this end, this film outlines the experience of the State Accountability and Voice Initiative (SAVI), a DFID-funded programme in Nigeria providing support to civil society, media and governmental organisations.

Learning and Results in World Bank Operations: Toward a New Learning Strategy - World Bank (IEG , The World Bank, 2015)
This report is the second in a program of evaluations that the Independent Evaluation Group (IEG) is conducting on the learning that takes place through World Bank projects. Learning and knowledge are treated as parts of a whole and are presumed to be mutually reinforcing.
Keywords: IMPORTANT

Strategy Testing: An innovative approach to monitoring highly flexible aid programs - Ladner, Debra (The Asia Foundation, 2015)
The international development community has increasingly embraced the idea that finding durable solutions to complex development problems requires new ways of working that move beyond industry norms. This paper makes an important contribution to the current debate by outlining an innovative monitoring system called Strategy Testing (ST). This is the third paper in the Working Politically in Practice paper series, launched together with the Australian Department of Foreign Affairs and Trade.

Effective Governance. Strategy for Australia’s aid investments - DFAT (Department of Foreign Affairs and Trade, Australian Government, 2015)

Forward Look - A vision for the World Bank Group in 2030 - World Bank (World Bank, 2016)

Strategic Framework for mainstreaming citizen engagemente in World Bank Group operations - World Bank (The World Bank, 2014)

Experiential Learning: Fostering lasting behavioural change - Norton, Brittney M. (Mercy Corps, 2016)
The term ‘experiential learning’ is often mistakenly used to describe any learning experience that involves participatory activities. This paper presents an overview of what true experiential learning is and how this form of learning allows for real-world application - thus promoting lasting behavioural change. Furthermore, it explains how experiential learning was adopted as the methodological core of the Prospects psychosocial programme in Liberia, which builds ‘pre-employment skills’ in 3,500 vulnerable youth aged 15-24 years. The goal of the paper is to provide other youth and education development practitioners with a resource that can be used to strengthen youth and behaviour change programmes through the incorporation of the experiential learning theory. In addition, this paper explains its application in the Prospects programme, before concluding with key considerations of such a design. 1

Donors' Learning Difficulties: Results, Relationships and Responsibilities - Eyben, Rosalind (IDS Bulletin, 2005)

Forget the money: De-linking technical assistance - Manuel, Clare (DFID-LASER Programme, 2016)

Introduction to SAVI's way of working - State Accountability and Voice Initiative (SAVI) - SAVI (DFID, 2015)
We are piloting a new approach to identifying and supporting our partners. This breaks with convention in many ways in order to improve impact. SAVI Approach Papers summarise key aspects of SAVI’s way of working. They explain what we do, and why – and link to relevant tools and frameworks. Our approach is summarized in...
Keywords: Practice

State Accountability and Voice Initiative (SAVI) - Approach Paper Series - SAVI (DFID, 2016)
We are piloting a new approach to identifying and supporting our partners. This breaks with convention in many ways in order to improve impact. Our approach is summarized in the Introduction to SAVI’s way of working. We have broken our approach down into key components – depicted in the form of our ‘knowledge tree’ –...
Keywords: IMPORTANT

Bringing Participation into Complexity-Aware MEL: What is the evidence? - Apgar, Marina; Higdon, Grace Lyn (2018)

It's All About MeE: Using Structured Experiential Learning (“e”) to Crawl the Design Space - Pritchett, Lant; Samji, Salimah; Hammer, Jeffrey (Center for Global Development, 2013)
This paper argues that within-project variations in design can serve as their own counterfactual, reducing the incremental cost of evaluation and increasing the direct usefulness of evaluation to implementing agencies. It suggests combining monitoring (‘M’), structured experiential learning (‘e’), and evaluation (‘E’) so as to facilitate innovation and organisational capability building while also providing accountability …

Supporting Learning? Exploring the relationship between grantee learning and grantmaking practice in the transparency and accountability sector - Ross, Jenny (INTRAC, 2015)
Learning is fundamental to work on transparency and accountability in complex environments. But how can funding practices best support learning?

Guidance Note: Evaluation Criteria - Chaplowe, Scott; Child, Keith; AF-TERG (Adaptation Fund, 2024)

Anatomy of Social Accountability 3.0: A working framework for moving forward - Guerzovich, Florencia; Aston, Tom (Florianopolis, SC, Brazil: Grupo Politeia, ESAG, University of the State of Santa Catarina and act4delivery, 2023)
This note presents the key components of a potential next generation of social accountability programming. The key aspects outlined emerge from a review of over 150 cases as well as tacit knowledge from dozens of practitioners (Guerzovich and Aston, 2023).The main thread of social accountability 3.0 and what distinguishes it from previous generations is a focus on its contribution towards more responsive systems and accountable social contracts. In particular, social accountability should be considered as an operational means to rework social contracts.Over the last two decades, the field has been defined by a supposed dichotomy between minimalist (i.e., “widget” based) approach or a maximalist (“go big or go home”) approaches. Yet, most practice sits somewhere between these extremes. The paper presents various options derived from practice; practitioners should choose whichever best fits their own particular circumstances.Those hoping to improve and expand their practice with a systems-lens may benefit from considering how they approach the key elements of social accountability 3.0.
Keywords: accountability; development; responsiveness; social accountability; social contract; systems

Teams that Do Development Differently - Khan, Jehanzeb; Fisher, Annette (Global Policy Journal, 2017)

SAVI Approach Paper 13: Measuring Value for Money and using Value for Money Analysis - SAVI (DFID, 2016)
SAVI has established its own framework for assessing Value for Money in annual performance – in relation to expenditure, economy, efficiency, effectiveness and equity. Routine tracking and analysis of expenditure and economy ensure that inputs are supplied and services delivered to partners in line with SAVI’s core values, whilst also meeting DFID requirements and competing...

Applied political economy analysis for human rights programs and campaigns: A guide for practitioners (second edition) - Pact (Pact, 2023)
This updated guide provides practical guidance to practitioners in the human rights sector and beyond on how to integrate Applied Political Economy Analysis

Evaluative Inquiry for Systemic Change: A Guide to Shift Beyond Fixes to Lasting Value - Gates, Emily F.; Vidueira, Pablo (SAGE Publications, Inc, 2025)
In a world where social, ecological, health, and other problems are influenced by multiple, intersecting systems, why do most interventions target single-factor solutions? Why does so much evaluation settle for incremental change, and how could it contribute instead to deeper, lasting, transformative change? Authors Emily F. Gates and Pablo Vidueira make two interconnected arguments in this book: they critique the "fixed" approach of traditional program evaluation and policy analysis, and they advance an alternative approach centered on changing systems and developing the value of efforts toward change. They demonstrate that systemic change that embeds evaluative inquiry is a theoretically supported, practical way to work toward fundamental social change with lasting impact.

Strengthening Advocacy and Civic Engagemetn in Nigeria - Chemonics (Chemonics International, 2018)

The Future is a Choice: The Oxfam Framework and Guidance for Resilient Development - Jeans, Helen; Thomas, Sebastien; Castillo, Gina (Policy & Practice, 2016)
This guide provides a framework for Oxfam staff to design programmes and campaigns that contribute to resilient development. Oxfam defines resilience as ‘the ability of women and men to realize their rights and improve their well-being despite shocks, stresses

How are Research for Development Programmes Implementing and Evaluating Equitable Partnerships to Address Power Asymmetries? - Snijder, Mieke; Steege, Rosie; Callander, Michelle; Wahome, Michel; Rahman, M. Feisal; Apgar, Marina; Theobald, Sally; Bracken, Louise J.; Dean, Laura; Mansaray, Bintu; Saligram, Prasanna; Garimella, Surekha; et al. (The European Journal of Development Research, 2023)
The complexity of issues addressed by research for development (R4D) requires collaborations between partners from a range of disciplines and cultural contexts. Power asymmetries within such partnerships may obstruct the fair distribution of resources, responsibilities and benefits across all partners. This paper presents a cross-case analysis of five R4D partnership evaluations, their methods and how they unearthed and addressed power asymmetries. It contributes to the field of R4D partnership evaluations by detailing approaches and methods employed to evaluate these partnerships. Theory-based evaluations deepened understandings of how equitable partnerships contribute to R4D generating impact and centring the relational side of R4D. Participatory approaches that involved all partners in developing and evaluating partnership principles ensured contextually appropriate definitions and a focus on what partners value.

The Clash of the Counter-bureaucracy and Development - Natsios, Andrew (The Center for Global Development, 2010)
In this essay, Andrew Natsios gives a first-hand account of what he finds most hinders USAID—layers of bureaucracy that misguide and derail development work.

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Le, Ha; Sah, Anjali (IDS, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to U$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.

NGOs Doing Development Differently - Green, Duncan (From Poverty to Power, 2017)
Report back from a meeting of international NGOs to set up a research and practice network on 'Doing Development Differently' that can complement other actors

Release the pressure on governance practitioners - de Weijer, Frauke; Hauck, Volker (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Improving development aid design and evaluation: Plan for sailboats, not trains - Kleinfeld, Rachel (Carnegie Endowment for International Peace, 2015)
How do reforms that require political engagement differ from traditional technical reforms? Why is political engagement different, and what are the implications for design and evaluation? How should development programmes that engage politics be designed? And how can those who fund or implement such programmes evaluate whether their efforts are contributing to reform? This report …
Keywords: IMPORTANT

Local Systems: a framework for supporting sustained development - USAID (USAID, 2014)

Two Tunes, One Dance: Keeping Programming Agile - Learning Lab (USAID Learning Lab, 2017)

How to Build Movements with Cyclical Patterns in Mind - Non Profit News | Nonprofit Quarterly - Algoso, Dave; Guerzovich, Florencia; Gattoni, Soledad (Nonprofit Quarterly, 2023)
The world changes too much for anyone who is invested in social change work to imagine that this work is linear and predictable. Opportunities come and go, whether caused by a pandemic or political shifts. This much most social movement leaders and activists intuitively understand. But what can be done with this realization? How might movement groups better prepare for moments of opportunity? We want to explore how we can create the changes we want to see by responding to the changes that are outside our control.

World Development Report 2017: Governance and the Law - World Bank (The World Bank, 2017)

Thinking and Working Politically – Are We Seeing the Emergence of a Second Orthodoxy? - Teskey, Graham (Abt Associates, 2017)
There now is a persuasive volume of evidence that demonstrates that capacity and technical knowledge alone are insufficient to change deeply entrenched political interests and bureaucratic norms. These critiques demonstrate that an understanding of power asymmetries is frequently the critical missing ingredient in project design and implementation. Many eminent thinkers have looked at the difference between success and failure in development, and all point to the primacy of domestic politics. This point has not been lost on development agencies and some have tried to provoke greater attention to the role that politics plays. However, this recognition is yet to pass into the mainstream of development practice. Despite the slow but sure accretion of this knowledge the international community seems to be wedded to doing development traditionally. The purpose of this paper is to consider the extent to which a ‘second orthodoxy’ is slowly emerging which can stand alongside, and in some cases may supplant, the ‘first orthodoxy’ of the traditional project framework. Care has to be taken in making this argument, as there is certainly no consensus within the development community on its importance, and even among advocates, there are slightly differing interpretations of what this second orthodoxy looks like. Further, it is not absolutely clear that the two orthodoxies can co-exist. The paper does not call for any ‘paradigm shift’ in how development practitioners conceptualise programs and projects, nor does it demand that the project framework be scrapped; the former would be impossible and the latter undesirable. Equally readers will find no claims that Doing Development Differently or ‘Thinking and Working Politically’ will always and everywhere guarantee better development outcomes. Rather, the paper seeks to summarise how the two orthodoxies differ, where the second orthodoxy now stands, and propose how it can be taken forward in practical terms.

The Art of Scaling Deep - Research in Summary - Fraser, Tatiana (The Systems Sanctuary, 2023)
Over the last 15 years the concept of scale has become a foundational part of the apparatus of the social and environmental change sector. A business mindset of growth has been seamlessly transferred to the social and environmental problems we are collectively trying to shift in the world. Scaling up, (influencing policy) has been considered the strategic pathway to systems change. Scaling out (spreading new models) is seen as a pathway to success. The allure of these scaling theories lies, in part, in their tangibility, and the easy way in which they can be measured. However this focus on growth has shifted our attention away from a series of messy truths. Sometimes bigger isn't better. Endless growth is not sustainable and our urgency to try to fix the problem and seek solutions may be part of the crisis we are in. One unintended consequence of this has been that another type of scale has been devalued and as a result, under-resourced. It’s a scale that values the slow steady work of deepening relationships. It recognizes the significance of context, building connections that bridge diverse communities and it prioritizes inner work and healing as integral components of the scaling process. We call this type of scale ‘Scaling Deep’ and we believe that adequately supporting it, and funding it, holds the greatest potential for long lasting systemic change. The purpose of this research has been to delve deeper into the art and craft of Scaling Deep. Ultimately, our goal is for it to become firmly ingrained within the recognized realm of social change, alongside the well-established concepts of scaling up and scaling out. We want practitioners who are Scaling Deep to be able to harness the wisdom and power of this work and to talk about it openly, with confidence and credibility. We want understanding of this approach to flourish and evolve and for it to be appropriately celebrated and supported. We want decision-makers to be informed and inspired by the principles and practices of scaling deep. For it to be embedded in theories of change as an essential component of decision-making processes within the wider change discourse. Importantly we want leaders who are Scaling Deep to have access to sufficient resources and to receive the care from the field that they need to thrive. We would like to see organisations that have the power to invest, to align their efforts with the profound impact that scaling deep aspires to cultivate in the world. Before we begin, let us be crystal clear. We are not opposed to scaling up and out as strategies for change. Innovation and scaling what is working is part of how we evolve as humanity. As social entrepreneurs ourselves, we have both done this twice over. We value it and we know it’s important. We recognize these are strategies for creating widespread impact and effecting positive change. Our intention here is not to dismiss or undermine the value of scaling up and out, but rather to encourage a broader and more holistic perspective that includes other dimensions of scale. There is a need to understand how the different scaling approaches can work together, rather than seeing them as hierarchical and disconnected. Our ultimate goal is to equip the change sector with a more inclusive, expansive, and powerful approach to tackling the myriad challenges we face, by exploring the potential of Scaling Deep as a transformational strategy for systems change.

From best practice to best fit: understanding and navigating wicked problems in international development - Ramalingam, Ben; Laric, Miguel; Primrose, John (ODI, 2014)

Putting theory into practice: how DFID is doing development differently - Wild, Leni; Booth, David; Valters, Craig (ODI, 2017)
Keywords: IMPORTANT

Monday morning in Kigali: what do you do when you get off the plane? Practical guidance for PDIA practitioners - LASER (DFID-LASER Programme, 2016)
In order to help enhance the effectiveness of donors and development practitioners on the ground, LASER has produced a range of practical guidance and tools. These are primarily intended for the international development community engaged in designing and implementing investment climate programmes, though can also be used more widely by other stakeholders across sectors. General guidance and tools: Monday morning in Kigali January 2016 - what do you do when you get off the plane? Practical guidance for PDIA practitioners
Keywords: IMPORTANT; Practice

Investment Climate Reform: Doing it Differently - Manuel, Clare (DFID-LASER Programme, 2015)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others). First synthesis paper - Investment climate reform: doing it differently June 2015 Drawing on our experience in taking a problem-focused approach to investment climate reform, we discuss in this peer-reviewed paper emerging lessons and reflections on what works, both in recent literature and in practical experience.

DFID Smart Rules: Better Programme Delivery - version VII (2017.04) - DFID (DFID, 2017)
Smart Rules provide the operating framework for the Department for International Development’s (DFID’s) programmes.
Keywords: IMPORTANT; Practice

A Governance Practitioner’s Notebook: Alternative Ideas and Approaches - Whaites, Alan; Gonzalez, Eduardo; Fyson, Sara; Teskey, Graham (OECD, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

DFID Smart Rules: Better Programme Delivery - version VI (2016.10) - DFID (DFID, 2016)
Smart Rules provide the operating framework for the Department for International Development’s (DFID’s) programmes.
Keywords: IMPORTANT; Practice

SAVI Approach Paper 4: Thinking and Working Politically - Supporting partners and staff through a participatory apporach to political economy analysis - SAVI (DFID, 2015)
Thinking and acting politically is central to the SAVI programme. We support staff and partners to analyse the power relations that shape change in their state, and to use this knowledge to inform their decision-making. This includes decisions made by SAVI state teams relating to the issues and partners they engage with and support, and...

It's the politics! Can donors rise to the challenge? - Unsworth, Sue (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Doing Development Differently at the World Bank: updating the plumbing to fit the architecture - Bain, Katherine A.; Booth, David; Wild, Leni (ODI, 2016)
Keywords: IMPORTANT

Case study: Embedding reform and exiting: LASER’s application of the hourglass approach to achieve sustainable results - Manuel, Clare (DFID-LASER Programme, 2016)
This case study describes how LASER has gone about enabling systemic change and sustainable uptake of reforms that address complex institutional problems in Kenya, Rwanda, Sierra Leone, Somaliland and Uganda. In each of these countries LASER has designed-in a sustainable approach from the start based on: (i) local ownership and leadership of reforms based on developing country (rather than donor) priorities; (ii) use of country (rather than donor programme) systems; and (iii) an understanding that the role of the donor / development practitioner is to support (rather than buy) reform. The case study uses LASER’s hour glass methodology, illustrated with examples from LASER interventions, to show how these principles guide LASER operations every step of the way.
Keywords: IMPORTANT; Practice

Mind the gaps: What's missing in political economy analysis and why it matters - Hudson, David; Marquette, Heather (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT